Chlorine dioxide fumigation improves kiwifruit peel appearance by selectively depleting flavonoid pigments without compromising eating quality - Jiacheng Teng; Rui Chen; Xuening Wu; Yanfei Hu; Zhengchen Tian; Weisong Li; Wendong Zhang; Xiaomei Ji; Xiaoqin Yang; Xuping Gong; Tiantian Li; Xiaoyan Mao; et al. (Postharvest Biology and Technology, 2026)

Developing radio frequency technology for enhancing the processing characteristics of gluten-free rice dough based on gelatinization degree - Dongsheng Hu; Yingqi Tian; Jiahong Yuan; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2026)

Elements migration revealed by scientific drilling in the Anninghe fault, western Sichuan, China: Implication for seismicity in the southeastern margin of the Tibetan plateau - Qing Wei; Xuan-Hui Yang; Jia-Yong Tian; Duo-Xing Yang; Hong-Rui Fan (Journal of Asian Earth Sciences, 2026)

Quality formation mechanism of shiitake mushrooms during multiphase microwave drying (MMD) - Zhenbin Liu; Jia Luo; Jiayi Zhang; Rui Weng; Wenchao Liu; Hongbo Li; Huan Cheng; Dong Wang; Hengchao E; Lu Tian; Haizhen Mo; Liangbin Hu (Food Control, 2026)

Efficient sludge reduction and phosphorus recovery in innovative coupled sequencing batch and worm reactor Process: Performance, mass balance and metagenomic mechanisms - Jingjing Zhang; Lipin Li; Xuanhe Yang; Siqi Chen; Zhe Li; Rui Li; Chunlei Wang; Yu Tian (Bioresource Technology, 2026)

Review on advances in small molecule inhibitors on the treatment of inflammatory bowel disease - Tingting Shi; Rui Wu; Yan Liu; Yuan Tian; Xin Meng (Molecular Biology Reports, 2026)

Impacts of speed limits on emissions, energy consumption and traffic efficiency - Shi-Teng Zheng; Junfang Tian; Rui Jiang; Bin Jia; Ying-En Ge (Transportation Research Part D: Transport and Environment, 2026)

Pathogenic mechanisms of Trichoderma hamatum, a postharvest pathogen causing fruit rot - Hai-Rui Wang; Xiong Xiong; Wen-Chao Li; Shuang-Jiao Ma; Yan-Xue Liu; Tong Liu; Ke-Xiang Gao; Chuan-Rong Li; Hui-Xiang Liu; Ye-Han Tian (Postharvest Biology and Technology, 2026)

Negative regulation of seed germination in Medicago truncatula by the lncRNA MtCIR1 under salt stress is associated with alternative splicing - Rui Tian; Xiaohan Sun; Mingui Zhao; Wen-Hao Zhang (Plant Science, 2026)

Multi-scale optimization method for metamaterial plates with compression-torsion coupling inertial amplification - Rui Zhang; Nian Long; Hanlin Fu; Lang Zheng; Bo Zhang; Jian Zhu; Zhenhuan Tian (Engineering Structures, 2026)

Silica‑calcium composite amendments increase the erosion resistance of soda saline-alkali soils under consecutive extreme rainfall events - Zhuo Tian; Dongli She; Weidong Liang; Hongde Wang; Rui Fu; Shuo Wang; Yinhao Bai (CATENA, 2026)

Nitrogen fertilization and straw returning boost soil animal energy flux via distinct trait- vs. density-driven pathways - Hangle Ren; Rui Wu; Siwen Yang; Ying Liu; Weijie Zhao; Yamin Peng; Xiaohong Tian; Rui Yin (Agriculture, Ecosystems & Environment, 2026)

Physics-informed graph inference and prediction for global state estimation in water distribution networks - Yacan Man; Xiao Zhou; Wenchong Tian; Rui Yuan; Kuizu Su; Zhiguo Yuan (Water Research, 2026)

Organic amendment quality and quantity govern microbial necromass contributions to soil carbon sequestration: a meta-analysis - Jiaqi Hao; Mengdi Wang; Yiting Chen; Hui Xia; Hailin Zhang; Pete Smith; Yapeng Jiao; Binbin Cao; Yan Gao; Jianglan Shi; Xiangtian Meng; Rui Yin; et al. (Soil Biology and Biochemistry, 2026)

Using spherical protrusions for simultaneous pressure pulsation mitigation and efficiency enhancement in a giant Francis turbine across a wide load operation - Lei Tang; Xiao-Wen Huang; Rui Zhao; Tian-Yi Shi; Wen-Quan Wang (Ocean Engineering, 2026)

Mechanisms of sedimentary phosphorus migration in response to salinization: Iron-phosphorus coupled cycling and “manganese curtain” inhibition - Rui Li; Zuobing Liang; Zaizhi Yang; Zelin Yue; Shaoheng Li; Di Tian; Zhi Zhang; Liang Xiao; Jianyao Chen; Lei Gao (Journal of Environmental Chemical Engineering, 2026)

One-step hydrophilic network for simultaneous boost in scaling prone cation removal and resistance to organic fouling of nanofiltration membranes - Rui Yu; Haonan Zhang; Yanqi Gan; Xupan Wang; Tian Wang; Jiahe Li; Mengqi Shi; Chenxi Dong; Feng Wu (Journal of Environmental Chemical Engineering, 2026)

Facile fabrication of MWCNTs@HBPA nanocomposite for efficient Nb(V) recovery: Performance evaluation and mechanistic insights - Congzhong Tian; Wenjie Zou; Rui Ma (Journal of Environmental Chemical Engineering, 2026)

Beyond flavor: dietary vanillyl alcohol, a D₂ receptor antagonist promoting sleep - Lijing Zhang; Yujie Yang; Dongmei Yang; Richard Ward; Zhenshuai Hu; Hao Chen; Mengli Lan; Cheng Xiang; Su An; Jiameng Dai; Ying Zhu; Xianrun Sun; et al. (Food Research International, 2026)

Maternal exposure to particulate matter during pregnancy and offspring liver function - Ziyi Zhou; Bin Sun; Yudiyang Ma; Ning Chen; Haibo Li; Wenpu Shao; Rui Tang; Lei Zheng; Meiqi Xing; Xinru Zhao; Yibing Zhu; Yaohua Tian (Environmental Pollution, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Spirofluorene-grafted triazine branched poly(aryl piperidinium) anion exchange membranes for high performance water electrolysis and flow batteries - Wei-Feng Yang; Yong-Xin An; Rui Guo; Han Yan; Tian-Tian Wang; Chang-Ping Liu; Yong-Mei Tian; Wen-Bin Sun (Chemical Engineering Journal, 2026)

A review of atmospheric black carbon research progress in China - Qi Zhou; Shunyao Wang; Shujun Bie; Junjie Cai; Yingjun Chen; Yuan Cheng; Xiang Ding; Jianwei Gu; Jie Li; Weijun Li; Dantong Liu; Jiaying Liu; et al. (Atmospheric Environment, 2026)

Study on upper bound solution of anti-overturning bearing capacity of pile-bucket composite foundation in sand - Guang-si Chen; Rui Zhou; Le Wang; Run Liu; Tian-liang Li (Marine Georesources & Geotechnology, 2026)

Genesis of the Jiawula Pb–Zn–Ag deposit in the Great Xing’an Range, NE China: constraints from fluid inclusions and S–Pb isotopes - Hongzhe Xie; Guiyuan Sun; Quzong Baima; Xinyu Gao; Ziwen Yang; Rui Tian; Lin Yang; Licheng Zhao; Zhiping Li (Journal of Asian Earth Sciences, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

LhCAT2-mediated crosstalk between reactive oxygen species homeostasis and anthocyanin biosynthesis enhances zinc tolerance in Liriodendron hybrid - Yongchao Ke; Yu Liu; Teja Manda; Tian Min; Rui Wang; Wenbin Su; Liming Yang (Journal of Hazardous Materials, 2026)

A simple osmotic intervention suppresses nanoparticle-induced bacterial persistence during environmental disinfection - Rui Sun; Yijin Tian; Siyang Xue; Yueting Cui; Yunchen Zhao; Shuaishuai Li; Jiawei Yuan; Xuanxuan Zhang; Chengdong Zhang (Journal of Hazardous Materials, 2026)

Gaussian Mixture Distribution stereo matching network for satellite images - Jiahao Rao; Rui Liu; Weiliang Tao; Jun Chen; Xin Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Prenatal Heat Wave Exposure and Renal Function in Early Childhood: Findings from a Chinese Birth Cohort - Yibing Zhu; Rui Tang; Yudiyang Ma; Ning Chen; Xinru Zhao; Wenpu shao; Yaohua Tian; Chong Miao (Environmental Research, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Quadruple multiscale networks enable rapid frictional energy dissipation in fiber/epoxy composites - Zhiqiang Shan; Xiaohua Jia; Yaotao Zhou; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Entropy-driven engineering in AFe2O4 spinel enabling broadband microwave absorption - Xinglai Yuan; Wei Li; Qiancheng Gao; Fan Zhang; Ye Yuan; Xiaohan Wang; Yanqiu Zhu; Mi Tian; Hailong Wang; Rui Zhang; Biao Zhao; Qinghu Wang; et al. (Chemical Engineering Journal, 2026)

Polymer-based hydrogen barrier coatings: Material design, mechanisms, and theoretical simulation - Zhuofan Li; Zhibin Chen; Lingwei Ma; Jinke Wang; Xin Guo; Rui Tian; Bowei Zhang; Huaiyuan Wang; Dawei Zhang (Chemical Engineering Journal, 2026)

Molten salt-assisted gasification unlocks graphitic nitrogen dominated porous carbons from biomass for high-performance zinc–air batteries - Yiwen Chen; Yangyang Chen; Changrong Zhong; Rui Liu; Gangyong Li; Yucan Zhu; Zhi Li; Minjie Zhou; Rui Tian; Binhong He; Wenyuan Xu (Bioresource Technology, 2026)

Unraveling the spatial paradox of multi-hazard mitigation: divergent impacts of urban form and function on heat and pluvial flood hazards - Bomeng Wu; Rui Sun; Zhaoren Wang; Ye Tian; Lanyu Qin; Hezi Bai; Mengyuan Chen; Huocheng Lin; Shuang Li; Shuanning Zheng (Natural Hazards, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Field‐Deployable RPA ‐ CRISPR /Cas12a Detection of Decapod Iridescent Virus 1 in Shrimp - Rui Wang; Yanfeng Wang; Lihan Wang; Yishuai Du; Huiqin Tian; Tianlong Qiu; Liang Chi (Journal of Fish Diseases, 2026)
Decapod iridovirus 1 (DIV1) is a highly lethal pathogen that infects decapod crustaceans including Litopenaeus vannamei , causing mass mortality in cultured shrimp and severe economic losses worldwide. The ATPase gene is a highly conserved region within the DIV1 genome, plays a critical role in viral replication and represents an ideal target for molecular diagnostic development. In this study, we established a rapid, sensitive and field‐adaptable detection platform for DIV1 by integrating recombinase polymerase amplification (RPA) with the CRISPR/Cas12a system. RPA enables efficient isothermal amplification of target nucleic acids, achieving exponential enrichment of the target nucleic acids and exerting the function of signal amplification. While the CRISPR/Cas12a system upon crRNA‐guided specific recognition of the amplicon, triggers robust trans‐cleavage activity against reporter probes for signal generation and readout. After systematic optimization, the RPA reaction was performed at 38°C for 10 min and the CRISPR‐Cas12a reaction was conducted at 37°C for 20 min. The integrated two‐step workflow completed detection within 40 min, with a limit of detection of 2.3 × 10 1 copies/μL. Specificity evaluation confirmed that the RPA‐CRISPR/Cas12a assay exclusively recognised DIV1 without cross‐reaction with other major shrimp pathogens. Further validation using clinical shrimp samples demonstrated stable and reliable performance, supporting its practical utility in aquaculture settings. In conclusion, the established CRISPR/Cas12a‐based detection platform provides a robust technical tool for early warning and on‐site rapid screening of DIV1, facilitating timely disease control and risk management in shrimp farming.

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Underground mine tunnel fire dynamics: Experimental investigation and AI-driven characterization of flame behavior - Jingmin Xu; Rui Tian; Ashish Kakoria; Aamir Iqbal; Tao Yang; Lina Zheng; Guang Xu (Tunnelling and Underground Space Technology, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Enhancing simulation accuracy of a semi-distributed conceptual hydrological model using satellite soil moisture products - Haotian Cai; Yi Nan; Rui Tong; Fuqiang Tian; Jingan Lin (Journal of Hydrology, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Light heterogeneity shapes contrasting ecological responses to photovoltaic arrays in Tibetan alpine grasslands - Lei Chen; Rui Weng; Wenhao Cong; Shuaihao Bai; Wenping Qin; Qiong Zhao; Saida Li; Yuhan Song; Jingxue Zhao; Lihua Tian (Journal of Environmental Management, 2026)

Efficient photocatalytic degradation of acetamiprid via Fe2O3/Fe-TCBPE activating peroxymonosulfate - Chenchen Li; Zhourui Wu; Rui Xu; Tai Xiang; Lin Tian; Yong Zhang (Journal of Environmental Sciences, 2026)

Effective photodynamic inactivation of curcumin in combination with ethylenediaminetetraacetic acid against Burkholderia gladioli pathovar cocovenenans - Xiu-Xia Tian; Jia-Jun Yan; Rui Huang; Quan Zhou; Qi-Ying Zeng; Yu-Ming Jiang; Zi-Hui Chen; Hai-Yan Wang; Bai-Sheng Li; Yong-Ning Wu; Wei-Liang Wu (Food Research International, 2026)

Dynamic response of muscle-inspired hierarchical tubular structure under lateral shock loading - Chang Ye Ni; De Long Cheng; Jian Hong Zhang; Gao Meng Cai; Rui Zhang; Tian Jian Lu (Engineering Structures, 2026)

Experimental study on seismic behaviour of full-scale glued laminated timber frame-glass wall composite structural unit - Tian Xia; Tao Zhou; Rui Xu; Hao Huang; Shao-Bo Kang (Engineering Structures, 2026)

Identification of distributed heat sources intensities with deterministic flow fields in ventilated spaces - Yemin Liu; Xiaoliang Shao; Rui Wang; Xiaohe Tian; Huifang Fan; Jianeng Cui (Building and Environment, 2026)

Calculation of hydrogeological parameters based on a high-flow long-duration water release test of multiple deep boreholes, Xiadian coalfield, North China - Fang Li; Rui Luo; Zhijia Yu; Wubin Gao; Jianggen He; Yu Ping; Shiyuan Tian; Zihan Wang; Tao Cheng; Colin G. Farquharson; Xinyi Wang (Hydrogeology Journal, 2026)

How does climate risk affect the grain production resilience: an analysis of mechanism pathways and mitigation strategies - Xiaohan Pei; Jintao Wang; Tian Qi; Rui Shi; Wenxin Liu; Minjuan Zhao (Climatic Change, 2026)

Non-nitrogen-fixing halophytes alleviate nitrogen limitation and decrease soil salinity through nitrogen transfer from nitrogen-fixing plants - Zehao Zhang; Tian Li; Yao Zhang; Rui Hu; Jiabao Li; Hongxiang Jin; Ying Fang; Zhaohua Lu; Jingkuan Sun (Plant and Soil, 2026)

Prevotella copri impairs bone mass via osteoclast activation in mice - Rui Li; Haiyan Zhang; Shiyong Xin; Tiantian Zeng; Wenchu Qian; Yawen Sun; Yunfei Cao; Yuxin Wang; Bin Li; Ming Tian; Hai Lin; Haifang Li (Molecular and Cellular Biochemistry, 2026)

Organic acids in four representative fermented alcoholic beverages: absorption, metabolic fate, and molecular mechanisms of health benefits - Xiaolu Tian; Rui Zhang; Haijue Zhang; Yi Liang; Yunxiang Ma; Zixuan Yang; Fuliang Han (Critical Reviews in Food Science and Nutrition, 2026)

PD-1⁺ CD8⁺ T cells: roles of PD-1 beyond an exhaustion marker - Jingyi Chen; Zixiang Chen; Liangjie Xu; Jieting Jia; Ke Rui; Jie Tian (Seminars in Immunopathology, 2026)

Hierarchical Studies in TRAP2 Mice Demonstrate that Neuronal Activation and Mitochondrial Networks Integration Constitute the Key Mechanism Underlying Painful Syncope - Xueyin Pu; Yulu Xia; Ziwei Ni; Changlei Zhu; Kunlong Zhang; Bozhi Liu; Rui Lin; Jingxuan Zhu; Hui Liu; Shujiao Li; Yunqiang Huang; Feifei Wu; et al. (Neuroscience Bulletin, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Bridging training–projection gaps in purely data-driven deep learning for runoff under climate change - Yiting Cen; Bin Yu; Rui Xiong; Mengqian Lu; Yong Tian; Feng Han; Peng Xu; Yi Zheng (Journal of Hydrology, 2026)

Amelioration of obesity-induced endothelial dysfunction by a synthetic ocean-derived peptide via regulating PPARα/γ pathway - Tiantian Zhou; Xinyi Chen; Yuehan Wang; Xutao Zhang; Lingchao Miao; Rui Tian; Yumeng Li; Yingying Feng; Xin Wu; Wai San Cheang (Food Research International, 2026)

Unveiling varietal specificity in non-destructive grape quality monitoring: Explainable AI and feature selection for sugar and organic acid prediction using NIR spectroscopy - Shijie Shi; Nina Tian; Qi Liu; Rui Yan; Liying Huang; Zhaoqiang Jin; Ke Liu; Xiaohai Tian; Yunbo Zhang (Food Research International, 2026)

Underestimation of industrial contributions to VOC fluctuation in the Hangzhou Bay: Insights from simultaneous measurements and ML-SHAP analysis - Kun Hu; Song Guo; Lei Shen; Zichao Wan; Xinshi Ni; Rui Tan; Xudong Tian; Bingye Xu; Limin Zeng; Qingyan Fu; Min Hu; Sihua Lu (Environmental Pollution, 2026)

Control of zeolite local microenvironment by organofluorination engineering toward efficient c-C4F8/C3F8 separation - Rui Sun; Zicheng Wan; Yaqi Wu; Yaohan Fu; Yang Zhang; Chenyang Yang; Heng Zhao; Ziqi Tian; Liang Chen (Chemical Engineering Journal, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Reprogrammable actuation in shape memory hydrogels with soft and hard magnetic particles - Ye Tian; Yuanyuan Bian; Zike Chen; Chang Zhao; Chengqian Zhang; Yi Song; Ye Qiu; Aiping Liu; Rui Xiao; Lu Dai; Huaping Wu (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Regulation of strain infectivity in Ophiocordyceps sinensis: insights into fungal-insect symbiosis and artificial cultivation - Tianle Liu; Lijuan Wu; Xinyi Zhao; Jun Tao; Yujie Qiu; Rui Li; Yongjun Zheng; Liang Liu; Mengliang Tian (Symbiosis, 2026)

Cross-instrument coal quality spectral analysis via a PDS-assisted fine-tuning calibration transfer method - Junlong Gao; Jiaxuan Li; Jiaxin Yin; Rui Gao; Zhihui Tian; Yang Zhao; Yu Bai; Lei Dong; Weiguang Ma; Lei Zhang; Wangbao Yin; Suoteng Jia (Analytica Chimica Acta, 2026)

Molecular characterization of a novel partitivirus isolated from Fusarium solani, the causal agent of tobacco root rot - Xiao Wu; Ying Wang; Rui Guo; Ya Rong Wang; Si Jun Li; Xiang Ping Zhou; Jie Zhong; Yan Song Xiao; Tian Bo Liu (Archives of Virology, 2026)

Curvature and Slope Control on Turbidity Currents and Sedimentation in Submarine Channels: A Numerical Study - Xinhao Wen; Yuechuan Han; Rui Zhu; Enxian Liu; Xiyan Lin; Yuchen Zhang; Yi Zhao; Yuhui Zhang; Jiajun Feng; Dongmei Tian (Journal of Marine Science and Engineering, 2026)
Submarine channels are critical conduits for sediment transport by turbidity currents, yet the quantitative influence of channel geometry on flow dynamics and sediment segregation remains poorly understood. Based on computational fluid dynamics, we constructed six three-dimensional numerical models of submarine channels with varying curvatures (R1–R3) and axial slopes (R4–R6) using ANSYS Fluent 17.2, with model settings informed by seafloor morphology from the South China Sea. The Eulerian–Eulerian multiphase model coupled with the standard k-ε turbulence model was used to simulate density fields, velocity structures, and sediment distributions. Results show that low-curvature channels exhibit symmetric density evolution and uniform sediment distribution, whereas high curvature induces pronounced asymmetry with a steep outer-bank density front and triggers secondary flow reversal. Increasing curvature also enhances flow thickness and radial mass flux. Increasing axial slope markedly elevates downstream velocity (0.09 to 0.16 m/s), reduces flow thickness, and shifts sediment distribution toward the inner bank without inducing secondary flow reversal. This study provides a parametric comparison of curvature versus slope effects on turbidity current dynamics and sedimentation patterns under fixed-bed, rectangular-channel assumptions. The findings offer a qualitative reference for interpreting sedimentary architectures in deep-water systems such as those in the South China Sea and analogous rift basins. Results are hypothesis-generating, pending further validation with field data and morphodynamic modeling.

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Selective separation of naphthalene sulfonic acids and salts from wastewater by electric field-assisted nanofiltration membranes - Yaning Tian; Jiansuxuan Chen; Rui Gao; Ruobin Dai; Zhiwei Wang (Water Research, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Mutual information and adaptive sparse learning for long term closed loop prediction of ship manoeuvring - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu (Ocean Engineering, 2026)

Data-driven ship manoeuvring modelling for long-term trajectory prediction using the progressive optimised identification framework - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu; Zhan Cheng (Ocean Engineering, 2026)

Ascosphaera apis-derived microRNA-like RNAs mediate cross-kingdom regulation of gene expression in western honeybee larvae - Xiaoxue Fan; Nian Fan; Tao Wu; Jing Kang; Jiarun Yang; Jing Tian; Xihan Luo; Dafu Chen; Jianfeng Qiu; Rui Guo (Journal of Invertebrate Pathology, 2026)

Ascosphaera apis invasion alters the expression pattern, alternative splicing and alternative polyadenylation of transcripts in the eastern honeybee larval gut - Jianfeng Qiu; Fangji Wang; Xiang Li; Tao Wu; Xin Jing; Zhenzhen Zuo; Jing Tian; Dafu Chen; Rui Guo (Journal of Invertebrate Pathology, 2026)

Earthworms counteract drought-induced impairment of wheat performance at the jointing stage regardless of microplastic type - Ruixin Du; Hanwen Cui; Ying Liu; Rui Wu; Yi Zhang; Chuanxiong Huang; Conghui Liu; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2026)

Dual-encapsulated γ-cyclodextrin liposomal hydrogel beads crosslinked with Ca2+-SHP for pH-responsive and targeted lutein delivery - Lanxin Zhang; Shengnan Wang; Xuejing Tian; Rui Wang; He Liu (Journal of Food Engineering, 2026)

Amorphous/crystalline heterophase induced S2− migration and oxidation for enhanced oxygen evolution reaction - Yue Huang; Jiejie Li; Yu Liu; Ying-Jie Ma; Lin Zhu; Fu-Rui Teng; Ziqi Tian; Ai-Dong Li (Chemical Engineering Journal, 2026)

Anti-adhesion nanofiltration membranes via a fluorine-rich microenvironment for broad-Spectrum micropollutant removal - Yanqi Gan; Rui Yu; Xupan Wang; Tian Wang; Jiahe Li; Feng Wu; Mengqi Shi (Chemical Engineering Journal, 2026)

Efficacy and Safety of Intravenous Thrombolysis with Tenecteplase in Patients with Wake-Up Branch Atheromatous Disease - Lili Zhu; Ying Zhang; Jiarong Li; Liang Song; Haoran Li; Yang Yang; Lijuan Liu; Shaolei Zhang; Xiaofei Gao; Weifeng Chen; Guo Rui; Haiqiang Qin; et al. (Translational Stroke Research, 2026)
Branch atheromatous disease (BAD), a subtype of acute ischemic stroke (AIS), is associated with a high risk of early neurological deterioration (END) and poor prognosis. Wake-up stroke (WUS), comprising 20%–30% of AIS cases, is typically excluded from thrombolysis because of unknown onset time. Using diffusion-weighted imaging/fluid-attenuated inversion recovery (DWI/FLAIR) mismatch, we evaluated the efficacy and safety of Tenecteplase (TNK) thrombolysis in patients with BAD-related WUS. We retrospectively recruited 1,062 patients from seven Zhengzhou hospitals between January 2021 and June 2025. The patients received either TNK (n = 338) or dual antiplatelet therapy (n = 724). Propensity score matching (PSM; 1:1, caliper 0.02) yielded 292 matched pairs. Early neurological changes were evaluated using the National Institutes of Health Stroke Scale (NIHSS), and 90-day outcomes were evaluated using the modified Rankin Scale (mRS). After PSM, TNK significantly reduced the risk of END (odds ratio [OR] = 0.425, 95% confidence interval [CI]: 0.262–0.689; P < 0.001). Patients treated with TNK were more likely to achieve good functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) with fewer poor outcomes (mRS ≥ 4). There were no significant differences in symptomatic intracranial hemorrhage, other bleeding events, or mortality among the groups. DWI/FLAIR mismatch-guided TNK thrombolysis appears to overcome the limitations of an unknown onset time in WUS and may counteract the progressive pathophysiology of BAD. TNK intravenous thrombolysis may be a safe and effective treatment for patients with wake-up BAD and DWI/FLAIR mismatches.

Natural longevity modulator: aging modulatory effects of Eurycoma longifolia Jack polysaccharides in C. elegans and D. melanogaster - Yan Liu; Hailing Wang; Rui Wu; Yuan Tian; Xin Meng (Biogerontology, 2026)

Effect of two double-stranded RNA viruses on the virulence of the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Xintao Liu; Hui Zhao; Xingbei Zhao; Rui Qiu; Siyuan Feng; Xiaoyuan Tian; Shouye Song; Shujun Li; Hongyan Liu (Archives of Virology, 2026)

High-Frequency Signal Recovery via the Constraint of Reflection Structure in f-x Domain - Chong Sun; Nan-ying Lan; Duo-ming Zheng; Hao-nan Tian; Shi-kai Jian; Lang Yang; Zhi-fang Ran; Rui-dong Liu (Applied Geophysics, 2026)

Minute‐Scale Adsorption of Diverse Marine Viruses Onto Clay Minerals - Lanlan Cai; Yuan Tian; Xuan Qiu; Yongle Xu; Hailiang Dong; Rui Zhang (Environmental Microbiology, 2026)
Viruses are ubiquitous biological entities with important roles in microbial mortality, genetic exchange and biogeochemical cycles. Clays, the most abundant mineral constituents on Earth, function as highly effective adsorbents for viruses, critically modulating their environmental persistence and ecological impact. However, the mechanisms and environmental drivers governing virus–clay interactions remain poorly understood. This study systematically investigates the adsorption kinetics of nine marine viruses onto a clay mineral (smectite, NAu‐2) under environmentally representative conditions. Viruses isolated from distinct hosts (heterotrophic bacteria, cyanobacteria and eukaryotic algae) and exhibiting diverse morphological features (myovirus, siphovirus, podovirus and tailless virus) were evaluated across gradients of NAu‐2/virus concentrations, pH, temperature and ionic strength. Elevated NAu‐2 concentrations (> 50 mg/L) induced rapid and near‐complete virus adsorption (90%–99%) within 1 min, while low concentrations (0.1–10 mg/L) yielded efficiencies from negligible to > 50%. Adsorption dynamics showed minimal correlation with viral morphology and instead depended on physicochemical properties. Electron microscopy revealed preferential viral localization at edge sites of NAu‐2, driven by charge heterogeneity from protonated alumina‐oxygen octahedra. These findings provide quantitative information on virus–clay interactions and offer key insights into the availability, transport and fate of viruses in the environment, paving the way for more accurate parameterization of biogeochemical cycling across ecosystems.

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Remote sensing-based estimation of global litterfall dynamics in forest ecosystems and its potential impact on soil respiration - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Lili Chang; Jia Tian; Rui Zhang (Remote Sensing of Environment, 2026)

Ship manoeuvring motion modelling based on dual-criterion feature selection and data augmentation - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu (Ocean Engineering, 2026)

Valorization of industrial carbide slag via microwave processing: A low-cost route to high-performance CaO-based CO2 sorbents - Fang Wang; Yi Dong; Shaojun Luo; Zixia Tian; Shuo Cui; Rui Cao; Zibin Pan; Ping Ning; Futing Xia; Jiayu Feng; Lijuan Jia (Journal of Environmental Management, 2026)

Application of layered double hydroxides (LDHs) derived catalysts for selective catalytic reduction of NOx with NH3 - Tian-yu Lv; Zuo-lin Cui; Rui-tang Guo (Fuel, 2026)

Unraveling the mechanism of improved gas cell structure in rice bread by radio-frequency-controlled gelatinization degree: A focus on protein-starch matrix and dough liquor interface - Dongsheng Hu; Yingqi Tian; Qianjie Xiong; Mengge Li; Rui Li; Shaojin Wang (Food Research International, 2026)

Structural and functional characterization of pectic polysaccharide fractions isolated from Choerospondias axillaris flesh - Qian Li; Rui Kang; Hongyi Lin; Yuanhang Wan; Taotao Dai; Panting Tian; Huashan Ling; David Julian McClements; Peiyi Shen; Jun Chen (Food Chemistry, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

Bio-inspired Zeta potential-matched design of natural rubber thermal interface materials with a compressed electrical double-layer for ultra-high thermal management capabilities - Rizheng He; Dongsheng Tian; Rui Tan; Bingxu Liu; Xinluo Yu; Huixing Li; Yaqing Liu; Dong An; Wei Feng; Chingping Wong (Chemical Engineering Journal, 2026)

Highly crystalline poly(heptazine imide) with improved intra- and inter-plane charge transport for efficient photocatalytic degradation of gaseous acetaldehyde - Dongying Wang; Lei Zhang; Rui Tian; Junjie Xu; Shuhao Sun; Beibei Cai; Ruijie Sun; Fei He (Chemical Engineering Journal, 2026)

Synergistic effect of tetrapropylammonium hydroxide and urea on hemicellulose fractionation with high-purity and high molecular weight - Rui Tian; Yi Ding; Bolang Zhu; Zhenhua Su; Baozhong Lü; Jing Bian; Mingfei Li; Zhengjun Shi; Pai Peng; Yuetong Kang; Feng Peng (Carbohydrate Polymers, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

The association of long-term exposure to PM1 with dyslipidemia in Chinese older adults and the modifying role of vitamin D - Pengjing Yao; Rui Zhang; Xuqiu Cheng; Xinyu Kou; Ziwei Tian; Jinmin Zheng; Yan Zhang; Xianwei Guo; Bing Hu; Changliu Liang; Yufeng Wen; Fangbiao Tao; et al. (Atmospheric Pollution Research, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

What are the driving factors and spatial-temporal characteristics of the landscape ecological risk of the Yellow River Delta? - Yao Zhang; Rui Hu; Tian Li; Zehao Zhang; Zhanyong Fu; Kaikai Dong; Jinzhao Ma; Zhaohua Lu; Jingkuan Sun (Environment, Development and Sustainability, 2026)

Integrated Transcriptomics and Machine Learning Reveal Lipid Metabolism Related Genes in Ischemic Stroke - Qiu-Lin Wang; Chang-Le Fang; Tian-Hao Bao; Rui-Ze Niu (Journal of Molecular Neuroscience, 2026)

Evaluation and characterization of aphid (Aphis craccivora) resistance in selected alfalfa genotypes - Xin Jiang; Jing Tian; Gang Li; Guy Smagghe; Zhong-Yi Li; Dao-Chao Jin; Zhou Li; Rui Dong; Xin-Yao Gu (Crop Protection, 2026)

Integrating carbon-based nutrient fertilization for urban soil management: Impacts on plant growth and microbial communities - Xihui Sun; Hong Liu; Rui Yu; Song Li; Xuemiao Tian; Huiwen Zhang; Lixin Niu; Yanlong Zhang (Urban Forestry & Urban Greening, 2026)

Conjugated organic polymer enables external-sacrificial-agent-free photocatalytic uranium extraction with efficiency boosted by oxygen pre-activation - Xuefeng Tian; Jipeng Li; Xuewen Cao; Jiacheng Zhang; Rui Huang; Peng Lin; Ning Wang; Yihui Yuan (Science Bulletin, 2026)

Multifaceted environmental footprints of spent coffee grounds valorization: from waste management to fuel and material production - Shuying Huang; Lan Wang; Jingwen Wang; Xi Tian; Mei Li; Xinyi Zhang; Dungang Gu; Tingting Hu; Rui Liu; Guanghui Li; Jiaqi Lu (Resources, Conservation and Recycling, 2026)

Algal ecological dynamics tracking model for studying hydrodynamic impacts on algae transport and accumulation in a shallow lake - Fei Du; Xiaobo Liu; Shiyan Wang; Chang Liu; Aiping Huang; Weijie Wang; Budong Li; Rui Gao; Xin Tian; Zhen Han; Hao Fan; Bi Wu (Journal of Hydrology, 2026)

A novel integrated model for risk analysis of soil PAHs and PTEs based on Monte Carlo simulation: a case study of Shenyang, China - Rui Zhong; Fulin Tian; Yiran Li; Zhengyu Liu; Jingyuan Wei; Hong Li; Peng Kang; Haibo Zhao; Zhisen Liu (Journal of Geochemical Exploration, 2026)

High-value utilization of chromium ore processing residue (COPR) through corn straw-soda roasting followed leaching processes - Cheng Tian; Zilong Li; Cunfang Lu; Rui Xu; Min Zhang; Lin Yang; Wenlin Xie; Zhengnan Zhong; Yuanyuan He; Juan Wen; Dan Luo (Journal of Environmental Chemical Engineering, 2026)

A Cu-based catalytic molecularly imprinted electrochemical sensor on paper for phthalylsulfacetamide detection in environmental water - Shuyan Miao; Jing Zhou; Zhen Xu; Yuting Wang; Rui Liu; Tian Gan (Journal of Environmental Chemical Engineering, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Flexible carbon cloth-supported novel Au@NiCo-LDH nanocomposite for an integrated strategy of nanoplastics adsorption and detection - Changmin Hou; Rui Chen; Shusheng Zhang; Mei Yan; Cheng Tian (Chemical Engineering Journal, 2026)

Dynamic electric field modulation via BaTiO3-based staggered-type heterojunction for all-solid-state lithium-sulfur batteries - Yancheng Yang; Sizhe Wang; Fei Liang; Haizhou Zhao; Yi Gu; Rujing Liu; Jian Sun; Yao Yao; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Experimental and numerical analysis of supply air jet in stratum ventilation for cooling - Yong Cheng; Yulong Xie; Rui Wang; Teng Li; Xue Tian (Building and Environment, 2026)

Relationship between expression of derived factor-1CXC chemokine receptor 4 in tumor tissues of patients with non-small cell lung cancer and postoperative lymph node metastasis - Zhanwu Zhang; Xiaoming Wang; Rui Tian; Kunpeng Duan; Xu Zhang (Journal of Molecular Histology, 2026)

Study on the effect of pore structure on water retention properties of compacted loess under wetting and drying cycle conditions - Zhiyong Zhang; Weixing Bao; Lei Tian; Zhiming Huang; Xiaolin Guan; Rui Chen (Bulletin of Engineering Geology and the Environment, 2026)

Interactive effects of microplastics, heavy metals, and soil microecology under different irrigation water sources - Rui Yang; Lijuan Huo; Hao Yang; Yan Gong; Gaiqiang Yang; Shuting Tian; Shuhui Cao; Xia Li; Qingwei Ding; Yaqiong Fan; Qi Liu (Applied Soil Ecology, 2026)

Effects of purple corn anthocyanins on feed intake, body weight, antioxidant activity, lipid metabolism, rumen fermentation, and rumen microbiota and function in perinatal goat does - Qi Lu; Yiqing Xu; Jixiao Qin; Shuanglong Xie; Rui Chen; Yiming Ban; Chengcheng Gao; Peiyao Li; Xu Wang; Xingzhou Tian (Animal Feed Science and Technology, 2026)

Qualitative analysis of chemical constituents and study on the biological activity of Polygonum perfoliatum L - Chaochen Yue; Ya Zhang; Juan Xue; Tian Lu; Lei Li; Yanjie Wang; Rui Zhou; Di Gao; Huifang Chai (Natural Product Research, 2026)

Stock discrimination and vertical migration of two gadoid species based on otolith stable isotope analysis - Rui Wu; Qinghuan Zhu; Julin Yuan; Satoshi Katayama; Yongjun Tian (Marine Life Science & Technology, 2026)

Quantifying the nonlinear interactions of 2D/3D building and green space morphology on land surface temperature across different urban functional zones - Haiyan Luo; Rui Zhou; Chunlin Li; Qun Ma; Xuening Fang; Yina Hu; Xinlin Lv; Zining Dong; Yujing Tian; Shubo Fang (Sustainable Cities and Society, 2026)

Experimental investigation on the dynamic characteristics of marine soft soil under temperature effects - Rui Rui; Yinjie Peng; Zijin Tian; Jinyuan Wang (Soil Dynamics and Earthquake Engineering, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

Leaching mechanism and kinetics investigation of ilmenite leaching assisted by iron powder - Tao Long; Long Xiang; Rui Liu; Congxue Tian; Li Li; Jiesong Liu; Wenrong Xiang (Minerals Engineering, 2026)

Synergistic recovering Fe, Al and biochar through biomass-reduction alkali roasting and wet magnetic separation for red mud (RM): behavior and mechanism - Rui Xu; Cunfang Lu; Min Zhang; Cheng Tian; Dan Luo; Lin Yang; Wenlin Xie; Zhengnan Zhong; Juan Wen (Minerals Engineering, 2026)

Statistical Postprocessing of Subseasonal Cumulative Precipitation Forecasts Using a Spatial Heterogeneity-aware U-Net - Shiyuan Liu; Wentao Li; Qingyun Duan; Rui Tian (Journal of Hydrology, 2026)

Four decades of Landsat data reveal the evolution of nitrogen and phosphorus components driven by human activities in the northern South China Sea - Di Tian; Xinfeng Zhao; Xingxian Li; Lei Gao; Zuobing Liang; Rui Li; Shaoheng Li; Zaizhi Yang; Chengxiang Sun; Jianyao Chen (Journal of Environmental Management, 2026)

New insights into deep nitrogen removal in WWTP effluent: Performance and mechanisms of autotrophic denitrification filters - Xinxin Tian; Rui Yang; Haoyong Li; Xinying Liu; Yan Dang (Journal of Environmental Management, 2026)

Opposite effects of R1234yf on the flammability limits of R600a refrigerant: Experimental and kinetic insight - Xueyan Wang; Shanzhu Hu; Rui Sun; Hua Tian; Gequn Shu; Zhao Yang (International Journal of Refrigeration, 2026)

Gliadin hydrolysate-chitosan bilayer nanoparticles for berberine delivery: Controlled release, enhanced antioxidant activity, and lipid digestion regulation - Xiaoxiao Li; Yi Zhao; Aimei Liao; Yinchen Hou; Xinrui Zhang; Hailong Tian; Luyang Wang; Jin Liu; Jinyang Zhang; Jihong Huang; Rui Tan (Food Chemistry, 2026)

Uncovering cryoprotective mechanism of natural deep eutectic solvents for highly efficient cryopreservation of Lactiplantibacillus plantarum - You Tian; Da-Wen Sun; Shu-Ti Zhang; Rui Hu; Zhiwei Zhu (Food Chemistry, 2026)

Effect of dry-blanching pretreatment and drying using radio frequency energy on the dehydration performance, structural and quality properties of tiger nuts - Mengge Li; Yingqi Tian; Liumin Fan; Dongsheng Hu; Rui Li; Shaojin Wang (Food Control, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

In situ reconstruction of defect-engineered bimetallic (DA)Ni/Mo–MOFs@TiO2 generates an anion-protected active hydroxides via: Towards corrosion-resistant seawater photoelectrolysis for hydrogen production - Yue Li; Peihua Li; Rufeng Tian; Xingzi Bian; Jian Wang; Rui Li; Wanggang Zhang; Jiancheng Wang; Yiming Liu (Chemical Engineering Journal, 2026)

Insight into cryopreservation mechanism of natural deep eutectic solvents (NADESs) from the transcriptomics perspective - Rui Hu; Da-Wen Sun; You Tian; Liang Xu; Libin Sun (Chemical Engineering Journal, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

Nitrogen-fixing bacteria and arbuscular mycorrhizal fungi alleviated nitrogen limitation in halophytes and reduced soil salinity in salt-aggregating and salt-secreting plants - Zehao Zhang; Tian Li; Rui Hu; Zhanyong Fu; Yao Zhang; Jinzhao Ma; Ping Wang; Jingkuan Sun (Plant and Soil, 2026)

Research progress on quorum-quenching strategies for membrane biofouling control - Hongwei Wu; Kuo Yang; Yifan Gao; Rui Xu; Yuzhang Feng; Yinning Wang; Huimin Lin; Siqi Hu; Gege Tian; Jiaying Li; Pingfeng Yu; Bing Zhang (ENGINEERING Environment, 2026)

Correction to: Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

Auxiliary-wrapper guided and multi-criteria filter based evolutionary band selection algorithm for hyperspectral image classification - Qijun Wang; Xiaowen Sun; Rui Chen; Guangyao Yan; Aibin Yan; Ye Tian; Xingyi Zhang (Swarm and Evolutionary Computation, 2026)

Complex magmatic system and high-melt fraction of the Changbai volcano revealed by ambient noise tomography with a dense array - Han Zhang; You Tian; Dapeng Zhao; Rui Gao (Journal of Volcanology and Geothermal Research, 2026)

Preparation of high-performance reverse osmosis membrane by “bridging” polyethylene glycol with tannic acid - Tian Wang; Rui Yu; Yanqi Gan; Zihang Zhao; Mengqi Shi; Xinxia Tian (Journal of Environmental Chemical Engineering, 2026)

AMS-Former: Adaptive multi-scale transformer for multi-modal image matching - Jiahao Rao; Rui Liu; Jianjun Guan; Xin Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Beyond synthetic scenarios: Weakly-supervised super-resolution for spatiotemporally misaligned remote sensing images - Quanyi Guo; Rui Liu; Yangtian Fang; Yi Gao; Jun Chen; Xin Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Deciphering the potential risks of Yersinia enterocolitica across multi-points in food chain: prevalence, biofilm, and cross-stage transmission routes - Zhiguo Fang; Juran Mao; Zongzong Chen; Yue Wu; Xueqin Zhao; Rui Tian; Ye Lv; Xiao Xiao; Jiaqi Yan; Xiuqin Lou; Jun Li (Food Research International, 2026)

Antioxidant activity and emulsifying properties of Dendrobium officinale polysaccharides with distinct structural characteristics - Cunchao Zhao; Weiqian Wang; Fanrui Li; Jun Sheng; Rui He; Lijun You; Yang Tian (Food Chemistry, 2026)

Enhancing identification confidence in non-targeted screening of emerging contaminants via an ensemble retention time prediction model: Applications in screening and ecological risk assessment - Ye Liu; Hua-Chun Liu; Tian-Hong Chen; Jian-Ping Deng; Rui-Fang Fan; Hong-Xuan Kuang; Yun-Jiang Yu (Environmental Pollution, 2026)

Quantified passivator deposition via drop-on-demand inkjet printing for high-efficiency inverted perovskite solar cells - Jinxin Yang; Hengyi Jiang; Rui Yang; Ziqi Zhu; Yaxi Liu; Lina Shen; Yalian Weng; Chengbo Tian; Liqiang Xie; Zhanhua Wei (Chemical Engineering Journal, 2026)

Roles of vertical light-conducting carriers applied in microalgal-bacterial biofilm for enhanced nitrogen and phosphorus removal - Yong-Sen Cao; Yong-Qi Cheng; Yi Liu; Xing-Rui Zhou; Cong-Cong Tang; Zhang-Wei He; Wen-Qiong Wang; Yu Tian; Xiaochang C. Wang (Bioresource Technology, 2026)

A new strategy to simulate daily spatial distributions of urban air pollutants based on land use regression in Wuhan, China - Ya Tian; Gang Xu; Rui Xiao; Hui Lin (Atmospheric Pollution Research, 2026)

Simultaneous prediction of air quality for multi-sites using intensified spatiotemporal graph convolutional network based on Gaussian data augmentation - Xinyu Zhang; Leiming Suo; Changwen Ma; Chu Zhang; Rui He; Muhammad Shahzad Nazir; Tian Peng (Theoretical and Applied Climatology, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Diagnostic Value of Fast Stroke Imaging for Salvageable Brain Tissue and Collateral Circulation in Stroke Patients - Dongxue Wang; Shuang Liang; Zhongzhen Yue; Ye Tian; Jing Zhang; Liyu Qiao; Rui Li; Junqiang Xu; Rui Chen; Fanxiang Meng; Yichao Wang (Journal of Medical and Biological Engineering, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Fabrication of Rare Earth-Doped Fe3O4/HAP Nanoparticles with Fluorescence and their Application in Food and Beverage Testing - Yulin Wang; Rui Wu; Yankun Zhang; Guanghui Tian; Jiawei Guo; Yapeng Li (Journal of Fluorescence, 2026)

Structural characterisation of a novel polysaccharide from pseudostellaria heterophylla fibrous root and its anti-inflammatory and antioxidant activities in vitro - Meng-Yu Li; Hai-Tian Deng; Ming-Zhu Ye; Li-Li Lu; Hong-Yuan Chen; Wen Rui (Natural Product Research, 2026)

How Chlorella vulgaris remove florfenicol from wastewater—— from the aspects of kinetics, mechanism, limiting factors and long-term regulation - Lin-Lan Zhuang; Kehan Zhou; Wanqing Tian; Rui Li; Yingdong Shi; Zhongzhong Wang; Jian Zhang (Water Research, 2026)

Genome-wide identification of TGA transcription factors in wheat and the TaTGA13 negatively modulates stripe rust resistance - Jiajie Liu; Rui Li; Mingjie Xiang; Xunyin Yuan; Yifan Tian; Xuanqi Zhang; Jingyao Wang; Jianhui Wu; Qingdong Zeng; Dejun Han (Plant Science, 2026)

Phosphorus remobilization triggered by reduction of manganese oxyhydroxides in newly-deposited estuarine sediments under warming conditions: Robust evidence from field investigations and a microcosm experiment - Rui Li; Zuobing Liang; Qirui Wu; Zaizhi Yang; Chenchen Yang; Di Tian; Shaoheng Li; Jianyao Chen; Lei Gao (Journal of Hydrology, 2026)

Straw incorporation mitigates polyethylene residual film-induced suppression of fungal necromass - Conghui Liu; Yapeng Jiao; Hanyu Guo; Yunli Ji; Rui Yin; Yongxiang Yu; Jianglan Shi; Xiangtian Meng; Xiaohong Tian (Journal of Hazardous Materials, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Iron-driven synergism among microbial functional taxa facilitates recovery from denitrification toxicity - Yongzhi Zhang; Xiaoxiao Li; Linjun Gao; Ping Ye; Rui Wang; En Zhou; Tian Sun; Miaoqing Xu; Rui Wan; Xiang Li (Journal of Environmental Management, 2026)

Efficient oxygen evolution in acidic electrolysis of water using copper loaded with iridium nanoclusters - Yanan Song; Bingxin Zhang; Tai Xiang; Huabin Wang; Yong Zhang; Xiaoning Tang; Lin Tian; Rui Xu (Journal of Environmental Sciences, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Metabolomics insights into the combined effects of boscalid and polystyrene microplastics on earthworms (Eisenia fetida): The critical role of pesticide dose and microplastics size - Zhiyuan Meng; Junting Shi; Rui Zhou; Yaqi Xiao; Xin Bao; Yaowen Cui; Sinuo Tian; Xiaojun Chen (Environmental Pollution, 2026)

Design and mechanical properties of anchorage system with variable stiffness and bending angle for CFRP cables: Experiment and simulation - Yanzhao Niu; Chenggao Li; Jingwei Tian; Qingrui Yue; Rui Guo; Guijun Xian (Engineering Structures, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Single-atom Fe engineered-PANI/AC/MXene composite flow electrode for sustainable water desalination and electroplating wastewater treatment - Rui Chen; Yuzhan Luo; Hui Wang; Youyu Tian; Zhiqun Xie; Hui Wang; Zhiwei Jiang; Anqi Wang; Kai Yan; Zongsu Wei (Chemical Engineering Journal, 2026)

Machine learning-assisted the directed evolution of descriptor for Mg-CO2 batteries - Zhe Xue; Rui Tan; Ming Ji; Jinzhong Tian; Hua Hou; Xinyu Zhang; Lianfeng Zou; Yuhong Zhao (Chemical Engineering Journal, 2026)

N6-methyladenosine attenuates tumor-associated macrophages M2 polarization via suppressing the translation of Snail - Yifan Tian; Jianxin Peng; Jiawang Zhou; Weifeng Yang; Yanxi Peng; Jianing Li; Yalan Rui; Haisheng Zhang; Guoyou Xie; Haoran Wang; Jiamin Wang; Jiexin Li; et al. (Science China Life Sciences, 2026)

Spatiotemporal dynamics of non-photosynthetic vegetation across China and their implications for carbon fluxes along climate gradients - Chunsheng Wang; Qingjiu Tian; Wenmin Zhang; Jia Tian; Lili Chang; Rui Zhang; Qianjing Li (Science China Earth Sciences, 2026)

Warming and precipitation alter soil viral community structure and functional characteristics in dryland wheat fields on the Loess Plateau, China - Jin Kou; Feiyan Zheng; Jiaxuan Lei; Ting Wang; Heling Wang; Kai Zhang; Rui Tian; Xiaodong Lyu (Plant and Soil, 2026)

Mechanistic Integration of Beta-Alanine–Carnosine Buffering and Glutamine Metabolism in Exercise-Induced Muscle–Brain Crosstalk: Implications for Aging, Neurodegeneration, and Cognitive Decline - Rui Wang; Yan Guo; Juan Li; Tian Peng; Xinghao Wang (Molecular Neurobiology, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Echinacoside Improves Memory Function and Bone Mineral Density in the Aged SAMP8 Mouse Model - Rong Zhou; Ge Tian; Jing Yu; Rui Wang; Ning Peng; Xingzhi Guo; Rui Li (Molecular Neurobiology, 2026)

Associations of Paternal Seminal Plasma Metals with their Spouses’ Unexplained Recurrent Spontaneous Abortion (URSA) Risk and the Potential Mediating Role of Oxidative Stress - Hanyan Xi; Rui Yang; Huaqiong Bao; Huiru Li; Youzhu Li; Francis L. Martin; Wei Chen; Liang Chen; Yan Sun; Yan-Yang Lu; Qingyu Huang; Meiping Tian (Biological Trace Element Research, 2025)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Robust building wireframe reconstruction: a hypergraph and transformer-enhanced framework for large-scale and real-world urban point clouds - Haoran Gong; Jing Liu; Rui Tong; Fuqiang Tian; Di Wang (International Journal of Remote Sensing, 2025)

Immunomodulatory Effects of Angelica Sinensis Polysaccharides on Juvenile Chinese Sturgeon (Acipenser sinensis): Physiological and Molecular Insights - Jianming Zhang; Tian Tian; Dezhi Zhang; Rui He; Debin Shu; Wei Jiang; Yacheng Hu (Fishes, 2025)
The Chinese sturgeon (Acipenser sinensis) is a critically endangered species with significant ecological and economic value. This study investigates the effects of Angelica sinensis polysaccharides (ASPs) on the antioxidant and immune responses of juvenile Chinese sturgeon through physiological and molecular approaches. Healthy juvenile Chinese sturgeon (n = 120, mean body weight 356.50 ± 92.87 g) were fed diets supplemented with 0%, 0.5%, 1.0%, and 2.0% ASP for 36 days. Results showed that ASP, particularly at 2.0%, significantly enhanced serum antioxidant capacity by increasing activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and reduced malondialdehyde (MDA) content. Immune indices, including immunoglobulins (IgG and IgM), complement components (C3 and C4), lysozyme (LSZ) activity, and antimicrobial peptides (AMPs), were also significantly elevated in the 1.0% and 2.0% ASP groups. Transcriptome sequencing of spleen and kidney tissues from the control and 2.0% ASP groups identified 151 and 467 differentially expressed genes (DEGs), respectively, with significant enrichment in immune-related pathways such as phagocytosis and the MAPK signaling pathway. Ten candidate immune-related genes (e.g., PDIA4, H-2Q9α, TTC39B) were validated by qRT-PCR, confirming the reliability of the RNA-seq data. This study demonstrates that ASP can enhance the antioxidant and immune responses of juvenile Chinese sturgeon, providing a potential natural immunostimulant for aquaculture. These findings offer a scientific basis for the conservation and sustainable production of this endangered species and highlight the need for further research on the application of ASP in sturgeon aquaculture.

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

Dielectric heating technology assisted for multi-objective processing of agricultural products: research progress, challenges, and future perspectives - Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Longlong Jiang; Rui Li; Shaojin Wang (Critical Reviews in Food Science and Nutrition, 2025)

Performance of heavy metals in the intertidal zone surface sediments of the Yellow River Estuary under water-sediment regulation scheme - Shan Shan Liu; Jin Ming Song; Xue Gang Li; Hua Mao Yuan; Li Qin Duan; Jun Ma; Feng Min Pan; Jian Wei Xing; Chen Long Feng; De Tong Tian; Zhi Bo Wang; Rui Wang (Marine Pollution Bulletin, 2025)

Dynamic characteristics of a novel floating offshore photovoltaic system with flexible rope-net connection - De-Qing Zhang; Hong-Wei Tian; Zhi-Ming Yuan; Shuang-Rui Yu; Jun-Feng Du; Hua-Jun Li (Ocean Engineering, 2025)

Arrangement optimization of wingsails subject to complex mutual aerodynamic interference: A numerical study - Ranqi Ma; Daize Li; Rui Zhang; Feng Tian; Zhiqiang Tang; Jianlin Cao; Yuhao Xie; Zihan Jing; Jijun Chen; Xiaowu Li; Lianzhong Huang (Ocean Engineering, 2025)

Ship manoeuvring model identification using mutual information clustering with stepwise regression structural optimisation under small-sample constraints - Xiufeng Zhang; Rui Tian; Haitong Xu; Xiuwen Liu; C. Guedes Soares (Ocean Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

The detection method of ammonia nitrogen concentration in water bodies based on hyperspectrum - Yahe Di; Tao Li; Hui Ran; Rui Yang; Fei He; Aixuan Li; Chenzhan Tang; Wenjing Tian (Journal of Water Process Engineering, 2025)

New insights into sink-source dynamics of mangrove for microplastics: Quantitative evidences from field observation and resuspension simulation - Rui Li; Chao Yan; Qirui Wu; Xiangmei Cheng; Hua Wang; Zaizhi Yang; Zuobing Liang; Di Tian; Ning Yuan; Lei Hou; Lei Gao (Journal of Hazardous Materials, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

DoLPHiN: a proposed architecture and technical implementation of a database of structural and functional properties of natural polysaccharides with health benefits - Yefu Xin; Yongling Cao; Shuheng Yang; Junhao Hu; Miao Tian; Jian Dai; Jing Shi; Bingcong Yu; Nike Gu; Xiangxu Hu; Rui Zhu; Qianni Duan; et al. (Food Chemistry, 2025)

Multi-task deep learning utilizing VOCs detected by HS-GC-IMS for geographical origin tracing and adulteration detection of turmeric powder - Xiao Han; Tong Wu; Shixin Cen; Jie Yong; Xinrang Tian; Xinyi Li; Rui Sun; Minghui Liu; Heshui Yu; Zheng Li (Food Control, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Recent advances in manganese-based materials for water remediation: Multipollutant adsorption and catalytic oxidation - Hanghang Wang; Guangfei Qu; Yingying Cai; Chenyang Yin; Yaxin Tian; Rui Xu; Xinxin Liu; Minjie He; Changyi He; Jiao Wei (Environmental Research, 2025)

A new insight of volatile organic compounds measurement in Kunming City, Southwest China: season variation, chemical characteristics, and ozone formation sensitivity - Jianwu Shi; Rui Zhang; Feng Jiang; Feng Xiang; Yaoqian Zhong; Xinyu Han; Senlin Tian; Ping Ning (Environmental Pollution, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

A pH/ROS dual-responsive hydrogel promotes diabetic wound healing by controlled release of O2 and EGCG to induce angiogenesis and immunomodulation - Yongcen Chen; Xuemin Ma; Yajuan Hu; Huiyue Wang; Peirong Zhou; Xiaoping Tian; Haofeng Wang; Yun He; Gang Tao; Rui Cai; Junliang Chen (Chemical Engineering Journal, 2025)

Corrigendum to “Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds” [Chem. Eng. J. Volume 522, 15 October 2025, 166981] - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Genetic loci and functional genes conferring deep-sowing tolerance across multiple environments in soybean - Rui Tian; Zhenqi Shao; Hua Zhang; Xinzhu Xing; Jiahao Chu; Youbin Kong; Zhanwu Yang; Wenlong Li; Hui Du; Huifeng Ke; Xihuan Li; Caiying Zhang (Theoretical and Applied Genetics, 2025)

Lysosome-dependent cell death: disease implications and potential therapeutic targets - Ahequeli Gemingnuer; Rui Yin; Yan Liu; Yuan Tian; Xin Meng (Molecular Biology Reports, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

Unveiling Differences in Source Apportionment and Optical Properties of Wintertime Carbonaceous Aerosols in Northern and Southern Chinese Cities - Rui Li; Qiyuan Wang; Jie Tian; Yong Zhang; TingTing Wu; Lu Qi; Yang Chen; Shaofei Kong; Suixin Liu; Jin Wang; Julian Shi; Yuemei Han; et al. (Aerosol Science and Engineering, 2025)

Dynamics of multiple rogue waves for (3+1)-dimensional variable-coefficient potential Yu-Toda-Sasa-Fukuyama equation - Yi-Lin Tian; Wen-Yuan Li; Nong-Sen Li; Rui-Gang Zhang; Ji-Feng Cui (Wave Motion, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Millimeter-scale interactions of nitrogen and potassium on denitrification, anammox, and Feammox in soil fertilization zones - Jingjing Lyu; Rui Tian; Runhua Zhang; Peng Chen; Xinxin Jing; Runqin Zhang; Kang Zhao; Yi Liu; Chenhao Lyu; Zhiguo Li (Journal of Environmental Sciences, 2025)

Air layer-engineered Cf@void@SiCnf composites for enhanced electromagnetic wave absorption - Wenzhao Geng; Limeng Song; Yilin Liu; Haoyuan Lei; Peng Liang; Linan Wang; Hailong Wang; Yanqiu Zhu; Mi Tian; Rui Zhang; Zhiyu Min; Bingbing Fan (Chemical Engineering Journal, 2025)

Aerodynamically assisted biomimetic multifunctional device for simultaneous fog water harvesting and triboelectric energy generation - Changzheng Li; Fuyuan He; Ruishi Gan; Ziyuan Liang; Jingying Dai; Mengzhen Liao; Tao Rui; Zhi Qun Tian (Chemical Engineering Journal, 2025)

Vertical distribution, optical properties, and source attribution of summer dust in southern Tajikistan: ground-based observations and model results - Zhongwei Huang; Qingqing Dong; Tian Zhou; Jianrong Bi; Rui Chen; Qiantao Liu; Sabur F. Abdullaev; Dilovar Nozirov; Khan Alam; Tianhe Wang; Wuren Li; Ze Li; et al. (Atmospheric Environment, 2025)

Fossil involucres and a nutlet of Ostrya (Betulaceae) from the upper Eocene of Shaanxi and their biogeographic implications - Jiao Huang; Hui Jia; Rui-Feng Yan; Xiang-Ning Meng; Zhuo-Chen Han; Tian-Qi Dong; Jian Pan; Cheng Quan (Palaeoworld, 2025)

Rapid recovery of bisphenol A-inhibited anammox biofilm systems by exogenous AHLs addition - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Xiangyu Zhang; Xinpei Guan (Journal of Water Process Engineering, 2025)

Dose effects of polyethylene microplastics on the degradation of phenanthrene in agricultural soils and its underlying mechanisms - Chengyue Liang; Weilian Fu; Lin Tian; Wumei Xu; Yong Zhang; Tai Xiang; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

A promising strategy for selective recovery of Nb(V) using IRA-410 ion exchange resin: Adsorption performance and mechanism study - Congzhong Tian; Rui Ma; Wenjie Zou; Shifei Sun; Zhengyao Li; Zhijun Zhang; Fang Zhou (Journal of Environmental Chemical Engineering, 2025)

Photocatalytic biorefining green closed-loop: Photocatalytic alkali lignin depolymerization in supramolecular solvent - Chengcheng Suo; Xiaochang Zhang; Xinai Li; Jifang Zhang; Hongru Zhang; Rui Teng; Wei Li; Sha Luo; Bing Tian; Qingjiang Pan; Chunhui Ma; Zhijun Chen; et al. (Journal of Environmental Chemical Engineering, 2025)

Comparative effects of improved schemes with shape adjustment and composite packaging on radio frequency heating of two-component rice - Yingqi Tian; Mengge Li; Jiahong Yuan; Dongsheng Hu; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Effect of radio frequency heating on structure and physicochemical properties of protein and starch based on gelatinization degree of rice flour - Dongsheng Hu; Gaoji Yang; Yingqi Tian; Mengge Li; Liumin Fan; Rui Li; Shaojin Wang (Food Research International, 2025)

Gel-fouling on the microfiltration membrane for wastewater reclamation and its suppression by using electric fields: from the viewpoints of spatiotemporal and force analysis - Xinran Wang; Rui Wang; Xiangyu Tian; Qi Shen; Liang Feng; Dingyu Xing (Environmental Research, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Ultra-long and rapid operating zinc metal batteries enabled by multifunctional polarizable interface stabilizer - Song-Lin Tian; Li Lin; Si-Yu Jiang; Li-Na Song; Hai-Rui Wang; Ping Nie; Li-Min Chang; Wan-Qiang Liu (Chemical Engineering Journal, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Stabilizing zinc anode with multifunctional glycine copper additive - Lang Chen; Yue Tian; Bing-Chen Liu; Bo-Xuan Zhang; Kang-Rui Ren; Zhuo-Yun Song; Pengfei Wang; Zonglin Liu; Qianyu Zhang; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Porphyrinized carbon quantum dots: A novel antibacterial nanomaterial for visualized and broad-spectrum treatment of drug-resistant infected wounds - Mengwei Zhang; Jingjing Ye; Jingyao Zhang; Zijian Tian; Lebin Gan; Qiang Wang; Rui Li; Diya Sun; Zishuo Pei; Ming Li; Minghui Liang; Tianbing Wang (Chemical Engineering Journal, 2025)

Nitrogen-oxygen radical generator-mediated in situ activation of live-cell prodrug for rational combination therapy - Ting Hou; Zi-Tao Shen; Wan-Ting Chen; Yang Song; Yin-Yu Yan; Zi-Jiang Luo; You-Yang Li; Yu-Ting Shan; Rui-Cheng Li; Tian-Yu Shen; Jia-Qin Long; Li Yin; et al. (Chemical Engineering Journal, 2025)

Global response of soil phosphatase activity to land reclamation and vegetation restoration - Huaisong Wang; Mingming Wang; Jialing Xu; Yibo Tian; Jinyu Bai; Lei Zhang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; Rui Guo; Tao Zhang (CATENA, 2025)

Differences in the home-field effects of litter decomposition modulate changes in soil microbial nutrient limitations: insights from eco-enzyme stoichiometry - Yongxia Meng; Peng Li; Lie Xiao; Jialiang Liu; Chaoya Zhang; Shutong Yang; Xiaoming Zhang; Yunqi Wang; Tian Wang; Rui Wang (CATENA, 2025)

Dynamics of lignocellulose degradation by acid: Kinetic insights into high-solid acid pretreatment at normal temperatures - Qianqian Yang; Rui Zhai; Yihang Tian; Mingjie Jin (Bioresource Technology, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Formation Control of Multiple UUVs Based on GRU-KF with Communication Packet Loss - Juan Li; Rui Luo; Honghan Zhang; Zhenyang Tian (Journal of Marine Science and Engineering, 2025)
In response to the problem of decreased collaborative control performance in underwater unmanned vehicles (UUVs) with communication packet loss, a GRU-KF method for multi-UUV control that integrates a gated recurrent unit (GRU) and a Kalman filter (KF) is proposed. First, a UUV feedback linearization model and a current model are established, and a multi-UUV controller-based leader–follower method is designed, using a neural network-based radial basis function (RBF) to counteract the uncertainty effects in the model. For scenarios involving packet loss in multi-UUV collaborative communication, the GRU network extracts historical temporal features to enhance the system’s adaptability to communication uncertainties, while the KF performs state estimation and error correction. The simulation results show that, compared to compensation by the GRU network, the proposed method significantly reduces the jitter level and convergence time of errors, enabling the formation to exhibit good robustness and accuracy in communication packet loss scenarios.

Reproductive toxicity of glyphosate and its main metabolite aminomethyl phosphonic acid (AMPA) on zebrafish (Danio rerio) - Tan Yu; Li Songyan; Liu Honglin; Huang Di; Tian Yiqun; Qu Rui; Tian Hailin; Zhang Shichao; Lv Yuanfei; Huang Yingping; Huigang Liu (Chemosphere, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

B2G: A novel framework for froth velocity estimation and quantification with graph neural networks - Rui Tian; Ziqi Lv; Xiu Liu; Meijie Sun; Yanan Tu; Zhiqiang Xu; Weidong Wang (Minerals Engineering, 2025)

Mechanistic insights into electric field-driven specific ion effects on nanoplastics aggregation in heavy metal co-contaminated aquatic systems - Yan Peng; Rui Li; Ying Tang; Xinmin Liu; Yaowu Zhang; Xinping Gao; Kai Wang; Rui Tian; Hang Li (Journal of Hazardous Materials, 2025)

Earthworms mitigate drought effects on microbial decomposition of straw under varying microplastic conditions - Chuanxiong Huang; Weijie Zhao; Hangle Ren; Rui Wu; Ying Liu; Hongxin Xu; Benhua Sun; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Perfluorooctane sulfonate exposure disrupts steroid hormone synthesis in rats via the gut-metabolism-testis axis - Weizhen Hua; Rui Yang; Md Nur Alam; Zhenbin Che; Wanqing Zhu; Meiping Tian; Yan-Yang Lu; Yan Sun; Qingyu Huang (Environmental Pollution, 2025)

Barn swallow (Hirundo rustica) transfers current-use pesticides from agricultural fields to houses - Jiahe Zeng; Ziqing Luo; Kaiying Guo; Li Tian; Rui Zhang; Xiaobo Zheng (Environmental Pollution, 2025)

Static and fatigue performances of clip anchorage system for FRP rod used in cable - Guijun Xian; Yanzhao Niu; Jingwei Tian; Chenggao Li; Qingrui Yue; Rui Guo (Engineering Structures, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

An integrated biorefinery strategy for fractionating high-molecular-weight hemicellulose and uncondensed lignin based on tetrapropylammonium hydroxide system - Rui Tian; Bolang Zhu; Jing Li; Xinyuan Zhang; Baozhong Lü; Jing Bian; Jialong Wen; Zhengjun Shi; Yuetong Kang; Feng Peng (Chemical Engineering Journal, 2025)

Spin-blockade effect of chiral multi-branch Au nanoparticles for mediating oxygen evolution reaction of electro-catalytic water splitting - Rui Tian; Lufei Huang; Ying Li; Dewei Zhang; Shenghong Ju; Baowen Zhou; Lin Yao (Chemical Engineering Journal, 2025)

Overexpression of KIF2C amplifies tamoxifen resistance and lung metastasis of breast cancer through PLK1/C-Myc pathway - Rui Tian; Jilin Kong; Hongyan Zang; Shuyan Li; Xiangjuan Liu; Yan Cheng; Gaofeng Ni; Liguo Gong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Cu+ -loaded complex adsorbent in acid modified bentonite for improving carbon monoxide (CO) capture - Jianwei Cheng; Yifan Li; Rui Zhang; Dezhi Ran; Zuyun Chen; Wenhao Hou; Qiang Fu; Zhiguang Tian (Process Safety and Environmental Protection, 2025)

Dietary Houttuynia cordata Thunb. extract supplementation influences on antioxidant enzymes, meat quality, and gene expressions in fresh rabbit Longissimus thoracis et lumborum meat - Xu Wang; Shuanglong Xie; Rui Chen; Jixiao Qin; Yiqing Xu; Chao Ban; Qi Lu; Xingzhou Tian (Meat Science, 2025)

Prediction and changing patterns of physicochemical properties of rice flour during radio frequency heating - Dongsheng Hu; Jiahong Yuan; Mengge Li; Yingqi Tian; Gaoji Yang; Liumin Fan; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Failure mechanism of anchored anti-dip rock slope subjected to strong earthquakes: Insights from large-scale shaking table tests - Shanbai Wu; Liangqing Wang; Hans-Balder Havenith; Jianlin Tian; Qiong Wu; Changdong Li; Rui Ke; Chenlu Wang; Xiaochao Bi (Engineering Geology, 2025)

Climate-driven spatiotemporal variation of soil erodibility in China - Lili Qu; Zheng Sun; Zhiyuan Tian; J.M. Schoorl; Rui Ma; Yan Zhao; Yihang Wu; Yin Liang (Environmental Impact Assessment Review, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Estimation of Soil Organic Carbon Stocks Utilizing Machine Learning Algorithms and Multi-source Geospatial Data in Coastal Wetlands of Tianjin and Hebei, China - Rui Yang; Mingyue Liu; Yongbin Zhang; Weidong Man; Jingfen Tong; Dong Liu; Qingwen Zhang; Caiyao Kou; Xiang Li; Yahui Liu; Di Tian; Xuan Yin; et al. (Chinese Geographical Science, 2025)

Association between serum elementomics of 48 elements and female fecundity: evidence from a nested case-control study in China - Tian Tian; Fang Liu; Li Li; Jing Wei; Kailibinuer Kayimu; Yu Fu; Huahua Jiang; Fei Kong; Rui Yang; Yuanyuan Wang; Xiaoyu Long; Jie Qiao (International Journal of Hygiene and Environmental Health, 2025)

Sensitivity analysis of system condition, sample structure, and material property to radio frequency heating characteristics of multi-component rice using computer simulation - Yingqi Tian; Mengge Li; Jinsong Zhang; Dongsheng Hu; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Impact of watershed-scale land restoration on soil microbial communities and their functions: Insights from metagenomic analysis - Rui Yang; Shaoqing Guo; Lijuan Huo; Gaiqiang Yang; Shuting Tian (Environmental Research, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

Multi-level ROS regulation to activate innate and adaptive immune therapies - Ke-Ke Feng; Cheng-Lei Li; Yi-Fan Tu; Shi-Cheng Tian; Rui Xiong; Bai-Sheng Sa; Jing-Wei Shao (Chemical Engineering Journal, 2025)

Contrasting Effects of Warming and Nitrogen Addition on soil CO2 Emission in a Semi-Arid Grassland on the Loess Plateau of China - Mingfeng Jiang; Zhun Tian; Rui Wang; Zihan Sun; Yang Peng; Chao Fang (Water, Air, & Soil Pollution, 2025)

Functional shift in soil microbiome with decline in photosynthetic carbon input signifies rapid decrease of soil organic carbon during alpine grassland degradation - Minghua Song; Rui Pang; Yuqiang Tian; Yikang Li; Guiqiang Wang; Xingliang Xu (Biology and Fertility of Soils, 2025)

Holographic approach for three-dimensional magnetotelluric modeling and CPU-GPU Parallel Architecture - De-Xiang Zhu; Shi-Kun Dai; Hong-Jun Tian; Qing-Rui Chen; Wen-Xue Zhao (Applied Geophysics, 2025)

Assessing CO2 storage mechanisms in marine shallow sediments to mitigate leakage risks from sub-seabed carbon storage: a numerical simulation study - Gang Hu; Xiangyi Yi; Xuanhua Tian; Rui Wang; Pengchun Li; Linxiong Peng; Xi Liang (Frontiers in Marine Science, 2025)
The geological storage of CO 2 in offshore saline aquifers has been implemented at various sites worldwide. While subsea sediments can serve as a critical barrier against potential leakage from deep storage formations, the mechanisms and storage capacity for CO 2 trapping within these sediments remain inadequately understood. This study developed a two-dimensional conceptual model of shallow sediments based on the Enping15–1 Carbon Capture and Storage (CCS) project site in the South China Sea. Furthermore, the CO 2 -water-rock reaction and storage mechanism were simulated using CMG-GEM, and the process of CO 2 leakage into the sediments was investigated. The results indicate that CO 2 leakage into the shallow seabed sediments is primarily sequestered through dissolution in pore water, accounting for 70% of the total sequestration, while residual and mineral trapping contribute 10–20%. The dissolution of CO 2 leads to pore water acidification, which triggers the dissolution of anorthite and K-feldspar under the prevailing initial geochemical conditions. Dynamic reaction behavior is mainly observed at the leading edge of the acidified plume. However, if the leakage rate exceeds a critical threshold, the advancing acidified plume front causes partial dissolution of previously precipitated carbonate minerals. The critical leakage rate is determined to be 0.2 m³/day for single-point leakage and 0.3 m³/day for multi-point leakage. Notably, multi-point, low-velocity leakage enhances secondary storage within the sediment, thereby reducing the risk of CO 2 release into the overlying seawater.

Identification of key genes linking bisphenols exposure and breast cancer - Zhen Wang; Meng Cao; Tian Gao; Xinyue Xu; Weihua Yu; Jiangzheng Liu; Rui Liu; Xiaodi Zhang; Fei Li; Chunxu Hai (Toxicology, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Impact of soil erosion-driven degradation on crop yield in black soils of Northeast China's Songnen Plain - Yan ZHAO; Zhiyuan TIAN; Rui MA; Lili QU; Yihang WU; Yin LIANG (Pedosphere, 2025)

Salty tide enhanced ecotoxicological risk of trace metals in the lower reach of the Pearl River, China via altering their phase partitioning and chemical speciation - Lei Gao; Chao Yan; Chenchen Yang; Rui Li; Qirui Wu; Di Tian; Lei Ouyang (Journal of Hydrology, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Cement-mortar lining failure and metal release caused by electrochemical corrosion of ductile iron pipes in drinking water distribution systems - Hao Guo; Rui Wang; Menghan Jiang; Yimei Tian; Yapeng Jin; Weigao Zhao; Chenwan Wang; Jianhua Yin (Journal of Environmental Sciences, 2025)

Honey-processed Astragalus polysaccharides exhibit enhanced Qi-tonifying effects via structural modifications and microbiome-metabolome regulation - Zhaohui Lin; Lili Lu; Wenlong Guo; Shuyu Han; Yufei Tian; Hongyuan Chen; Wen Rui (Food Bioscience, 2025)

Enhanced gut damage and microbial imbalance in bullfrog tadpoles (Lithobates catesbeiana) exposed to polystyrene microplastics under high-temperature conditions - Zhilong Wang; Jun Xie; Guangjun Wang; Huirong Yang; Zhifei Li; Kai Zhang; Rui Shu; Wenping Xie; Jingjing Tian; Hongyan Li; Wangbao Gong; Yun Xia (Environmental Pollution, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Unraveling thermo-oxidation degradation pathways of polymers by in-situ differentiating the alkyl-related reactive oxygen radicals - Yue Hou; Jiao Li; Guofeng Tian; Rui Tian; Chao Lu (Chemical Engineering Journal, 2025)

Single stem cell encapsulation by MnO2 doped hydrogel for robust bone regeneration - Yu Tian; Pengxia Zhang; Zhen Ma; Mengya Li; Yali Fan; Rui Guo; YanFeng Li; Yingying Zhang (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Preparation of Nitrogen-Doped Biomass-Based Carbon Quantum Dots and their Application to Fe3+ Detection and Bioimaging - Rui Lv; Liyu Wu; Fuli Tian; Hongmei Bai; Dongke Huang; Yanqiu Lei; Fenrong Liu (Journal of Fluorescence, 2025)

High Yield of Prodigiosin by Serratia marcescens Ka3 Using Additive Huangshui, a Byproduct of Chinese Liquor (Baijiu) - Chuan Wang; Zhongxing Gao; Rui Han; Yaomei Tian; Hongjun Fan; Yuliang Zhang (Current Microbiology, 2025)

Emerging eutectogel materials: Development, synthesis, properties, and applications in food science - Rui Hu; Da-Wen Sun; You Tian (Trends in Food Science & Technology, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Isotope tracer study of soil erosion in a typical sub-watershed in the eastern Tianshan Mountains, China - Ninglu Zhang; Jianjun Yang; Wenli Xing; Xinyu Liu; Feifei Sheng; Wanqing Zhao; Zhiguang Zhang; Ziqi Tian; Rui Chen (Journal of Environmental Radioactivity, 2025)

Computer simulation analysis to improve radio frequency heating uniformity of multi-component rice samples by screening of sample structure - Yingqi Tian; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Permafrost thawing characterization in engineering scale by multi-geophysical methods: A case study from the Tibet Plateau - Junkai Ge; Huaifeng Sun; Rui Liu; Zhiyou Huang; Bo Tian; Lanbo Liu; Ziqiang Zheng (Engineering Geology, 2025)

Combining the bridging effect of tannic acid and solution activation for improving the lithium/magnesium separation performance of nanofiltration membrane - Tian Wang; Yajiao Long; Rui Yu; Yanqi Gan; Haonan Zhang; Jiahe Li; Mengqi Shi (Desalination, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Constructing a dual-layer PTFE nanofiltration membrane for enhanced salt solution permeability - Fuxin Qiu; Fan Liu; Rui Tian; Xutong Han; Kaikai Chen; Qinglin Huang (Desalination, 2025)

Physical-washable Revivable biomass membrane with high separation Rates against harsh conditions for sustainable treatment of wastewater containing emulsified oil - Yunhao Pan; Tiancheng Zha; Yanan Zhu; Yibo Zhang; Xunming Tian; Aiwen Wang; Rui Wang; Dongmei Liu; Wei Wang; Shouzhu Li (Chemical Engineering Journal, 2025)

Hydrogel-elastomer hybrid integrated with radiative and evaporative cooling for passive temperature-adaptive regulation - Libin Sun; Da-Wen Sun; Liang Xu; You Tian; Rui Hu; Zhiwei Zhu (Chemical Engineering Journal, 2025)

Exploration the effect of air pollution on the incidence of myasthenia gravis: An empirical study from Chengdu - Rui Zhou; Tianjun Li; Keyi Tian; Lei Huang (Atmospheric Pollution Research, 2025)

The tumor suppressor SALL2 opposes chemotherapeutic resistance in breast cancer - Qiji Li; Chenxin Li; Yuhao Zhang; Zihan Zheng; Yun Wang; Yingqian Yang; Qingqing Zhu; Rui Wang; Wanhui Xu; Chengming Zhu; Qin Tian; Meng Wang; et al. (Molecular and Cellular Biochemistry, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Evaluating the Centre‐Periphery Hypothesis Through Genomic Phylogeographical Comparisons of Two Sister Species of Liquidambar in East Asia's Tertiary Relict Forests - Tian‐Rui Wang; Wu‐Qin Xu; Hans‐Peter Comes; Xin‐Yi Zhang; Jun Chen; Yin‐Gang Li; Ying‐Xiong Qiu (Journal of Biogeography, 2025)
Aim Understanding the spatial distribution of genetic variation within species is a central tenet in evolutionary biology and conservation biology. This study explores how historical demographic processes and/or environmental factors interact to affect contemporary genetic variation and adaptive potential, with a specific focus on testing the ‘centre‐periphery’ hypothesis (CPH). Location Subtropical China. Taxon Liquidambar. Methods We combined comparative phylogeography, landscape genomics and niche modelling to investigate the interplay between demographic history and past/current environmental factors in shaping genetic variation in Liquidambar formosana and L. acalycina , a sister pair of East Asia's Tertiary relict forests. Results In both species, core populations occupied highly suitable habitats at highest densities. Consistent with the CPH, population genetic diversity decreased, and differentiation increased, from centre to margin in L. acalycina , but not in L. formosana , likely reflecting different demographic histories and different relative contributions of geography, past (LGM) and current climates to their present‐day genetic variation. In addition, L. formosana showed higher adaptive potential to future climate change than L. acalycina . Main Conclusions This study demonstrates that differences in contemporary genetic variation and adaptability among closely related species can be explained by contrasting demographic responses to multiple geographic/climatic factors. In turn, it should also expand our understanding of the CPH, while informing future conservation efforts for these two study species.

TadpoleTraits : A Global Database on Morphological Traits of Tadpoles of Anura - Yanfang Song; Rui Tian; Yongle Wang; Pingfan Wei; Tao Zhang; Shuaiwei Luo; Zhiyong Yuan; Weiwei Zhou (Global Ecology and Biogeography, 2025)
Motivation Functional diversity is an important dimension of biodiversity. In animals, most species have complex life cycles, such that the same species can display great differences in traits and ecological roles across different life history stages. Consequently, the patterns and driving factors of functional diversity can vary considerably among the different life stages. However, research on stages other than adults is rare, with data scarcity being a potential reason. The order Anura of Amphibia is a highly diverse group of terrestrial vertebrates, comprising more than 7800 species. Anurans have complex life cycles, and our knowledge about functional traits of the larval stage is extremely limited. To fill this gap, we collected morphological traits of tadpoles globally and compiled a database covering 1993 species to facilitate future studies. This database can help us gain a more comprehensive understanding of anuran biodiversity. Additionally, it offers a valuable tool for testing ecological and evolutionary hypotheses related to complex life cycles in animals. Main Types of Variables Contained Twenty‐three traits collected from literature and 11 traits obtained by image measuring. Spatial Location and Grain Global. Major Taxa and Level of Measurement Anura, species. Software Format xlsx.

Predictive maintenance for offshore wind farms with incomplete and biased prognostic information - Rui He; Zhigang Tian; Yifei Wang; Yinuo Chen; Ming J. Zuo (Ocean Engineering, 2025)

A novel tannic acid/iron/hydrophilic polymer nanofiltration membrane for small organic pollutant/salt separation - Yajiao Long; Yanqi Gan; Xiong Yao; Tian Wang; Haonan Zhang; Rui Yu; Jiahe Li; Mengqi Shi (Journal of Environmental Chemical Engineering, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Influence of geogrid reinforcement on the cracking characteristics of expansive soils: A laboratory study - Rui Zhang; Yu Zhou; Yipeng Guo; JianLong Zheng; Yufan Deng; Tian Lan (Geotextiles and Geomembranes, 2025)

Robust lubricity and multifunctional water-based lubrication system induced by ionic liquids with its interfacial self-assembly behavior and unique hydration structure - Mengyao Liu; Yingying Yao; Bingyu Tian; Kun Cui; Ping Wen; Rui Dong; Mingjin Fan (Chemical Engineering Journal, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Comparative chloroplast genome analysis of the medicinal species in Rubus: Insights into genomic characterization and phylogenetic relationships - Jiayu Jiang; Rui Tian; Ruolan Wang; Shuang Wang; Dequan Zhang (Plant Systematics and Evolution, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Specific cation effects on soil water infiltration and soil aggregate stability–Comparison study on variably and permanently charged soils - Shishu Yang; Rui Tian; Haiyang Wang; Yekun Zhang; Hang Li (Soil and Tillage Research, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Gelation melioration of clam Meretrix meretrix surimi based on the interactions with different plant/animal proteins - Lin-Da Zhang; Yue Liu; Ying-Rui Wang; Tian-Qi Zhou; Jia-Cheng Liu; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Phases partitioning and occurrence forms of arsenic, chromium, and vanadium in a tidal reach of the Pearl river estuary, South China - Lei Gao; Chao Yan; Chenchen Yang; Rui Li; Qirui Wu; Di Tian; Lei Ouyang (Environmental Pollution, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Effect of torrefaction pretreatment on catalytic pyrolysis of bagasse: A study on torrefaction method and atmosphere - Rui Liao; Xiaojie Tian; Liangliang Fan; Hui Li; Yuan Zeng; Linyao Ke; Qiuhao Wu; Roger Ruan; Yuhuan Liu; Yunpu Wang (Chemical Engineering Journal, 2025)

Recyclable thermally conductive nanocomposites based on interpenetrating network of boron nitride nanosheets and nanoribbons - Caiyue Huang; Xiaohua Jia; Rui Tian; Zhaofeng Wang; Haojie Song (Chemical Engineering Journal, 2025)

Screening heat-resistant energetic molecules via deep learning and high-throughput computation - Jian Liu; Jie Tian; Rui Liu; Yuechuan Tang; Chunming Yang; Junhong Zhou; Chaoyang Zhang (Chemical Engineering Journal, 2025)

Experiment and Peridynamics Simulation on Failure Mechanical Behavior of Cylindrical Sandstone Containing Two Persisting Fissures Under Conventional Triaxial Compression - Sheng-Qi Yang; Heng Li; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Wen-Ling Tian; Yun-Jin Hu; Yong Niu (Rock Mechanics and Rock Engineering, 2025)

Anti-inflammatory effect of multi-dose tranexamic acid in hip and knee arthroplasty: a systematic review and meta-analysis of randomized controlled trials - Chen Rui; Guangchun Dai; Chuwei Tian; Shaoyang Zhou; Yucheng Gao; Mumin Cao; Wei Wu; Shengbo Qin; Yunfeng Rui (Inflammopharmacology, 2025)

Effect of Particle Size, Sphericity, and Distribution on Seepage in Granular Porous Media - Bo-bo Xiong; Rui Kuang; Ping Zhang; Bin Tian; Hong-hu Gao; Qian Zheng; Yu-qin Li (Geotechnical and Geological Engineering, 2025)

Experimental study on direct contact condensation of steam bubbles with non-condensable gas at high Reynolds numbers - Taikun Guo; Junying Hong; Rui Han; Ruifeng Tian; Sichao Tan; Jiming Wen (Annals of Nuclear Energy, 2025)

Quantitatively distinguishing colloidal composition, surface property of differently sized particles for permanently and variably charged soils - Linqiao Yu; Aizhou He; Rui Tian; Xinmin Liu; Hang Li (Applied Clay Science, 2025)

Taloring sawdust derived hydrochar via red mud for cadmium removal: Electron transfer insight and recyclability assessment - Ting Cui; Dingxiang Chen; Ran Duan; Fan Yang; Danting Li; Lin Tian; Yong Zhang; Huabin Wang; Rui Xu (Chemosphere, 2025)

Chicken adipose tissue is differentially involved in primary and secondary regional immune response to NDV through miR-20a-5p-NR4A3 pathway - Yi Jiang; Rui Zhang; Xinxin Xu; Xiangnan Wang; Yufei Tian; Wei Zhang; Xiaoli Ma; Chaolai Man (Veterinary Immunology and Immunopathology, 2025)

Parametric investigation of suction actuators on the tunnel wall for alleviating pressure interactions in high-speed maglev train/tunnel system - Zheng-Wei Chen; Zhan-Hao Guo; Yi-Qing Ni; Zi-Jian Guo; Tian-Tian Wang; En-Ze Rui; Guang-Zhi Zeng (Tunnelling and Underground Space Technology, 2025)

A novel ensemble framework based on intelligent weight optimization and multi-model fusion for air quality index prediction - Shijie Qian; Tian Peng; Rui He; Jie Chen; Xuedong Zhang; Muhammad Shahzad Nazir; Chu Zhang (Urban Climate, 2025)

Improvement of ecological structure and function in phosphorus tailings-based soils through phosphorus-solubilizing bacteria inoculation and magnetic field treatment - Caiyue Jin; Xinxin Liu; Bangjin Chen; Guangfei Qu; Yaxin Tian; Fenghui Wu; Jieqian Yang; Rui Xu; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Development and characterization of a γ-PGA/PVA/SDBS cross-linked network foam for dust suppression in tunneling construction - Xinjiao Tian; Yixiang Huang; Qiang Zhang; Hongxiang Wang; Jinqian Zeng; Chaoqun Yuan; Jiefeng Pan; Rui Wang; Zhenming Li (Journal of Environmental Chemical Engineering, 2025)

Gelation improvement of low-salt Chinese shrimp (Fenneropenaeus chinensis) surimi gel by L-arginine - Yue Liu; Lin-Da Zhang; Ying-Rui Wang; Tian-Qi Zhou; Yu-Qiao Wang; Jia-Nan Yan; Bin Lai; Ce Wang; Hai-Tao Wu (Food Chemistry, 2025)

Radio frequency inactivation of Bacillus cereus and natural microbiota in brown rice: Evaluation of inactivation kinetics and germination capacity - Gaoji Yang; Dingting Zhou; Juanjuan Xu; Yingqi Tian; Rui Li; Shaojin Wang (Food Control, 2025)

Deciphering the mineral code of urinary stones: A first look at zinc isotopes - Ziyang Ding; Guilin Han; Yu Tian; Rui Qu; Jinke Liu; Di Wang; Ye Zhao (Environmental Pollution, 2025)

Reversibility of polystyrene nanoplastics-induced disruption of testosterone biosynthesis in mice: The role of histone modifications - Yan-Yang Lu; Rui Yang; Meiyi Cao; Lu Lu; Wanqing Zhu; Weizhen Hua; Meiping Tian; Yan Sun; Qingyu Huang (Environmental Pollution, 2025)

Two-stage continuous cultivation of microalgae overexpressing cytochrome P450 improves nitrogen and antibiotics removal from livestock and poultry wastewater - Rui Xiao; Chang Tian; Haijun Wang; Hui Zhang; Huan Chen; Howard H. Chou (Bioresource Technology, 2025)

The flavonoid metabolic pathway genes Ac4CL1, Ac4CL3 and AcHCT1 positively regulate the kiwifruit immune response to Pseudomonas syringae pv. actinidiae - Chao Ma; Wei Liu; Xiaofei Du; Chao Zhao; Runze Tian; Rui Li; Chenxiao Yao; Lili Huang (Plant Molecular Biology, 2025)

The Effect of Disc Degeneration on the Biomechanical Response of the Lumbar Spine under Vibration Loading Condition - Bin Zhang; Tian-Cheng Li; Xin Wang; Rui Zhu; Cheng-Fei Du; Yuan Xie (Journal of Medical and Biological Engineering, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

Underwater Target Detection with High Accuracy and Speed Based on YOLOv10 - Zhengliang Hu; Le Cheng; Shui Yu; Pan Xu; Peng Zhang; Rui Tian; Jingqi Han (Journal of Marine Science and Engineering, 2025)
Underwater target detection exhibits extensive applications in marine target exploration and marine environmental monitoring. However, conventional images of underwater targets present challenges including blurred contour information, complex environmental conditions, and pronounced scattering effects. In this work, an underwater target detection method based on YOLOv10 is designed, and the detection performance is compared with the YOLOv5 model. Experimental results demonstrate that the YOLOv10 model has a mAP50 of 85.6% on the URPC 2020 dataset, improving the mAP50 by 1.2% than that of YOLOv5. This model exhibits high detection accuracy and high proceeding speed, which provides a promising support for precise and fast underwater target detection.

An effective strategy for high-value utilization of chromite ore processing residue (COPR) through reductive alkali roasting and physical separation - Cheng Tian; Cunfang Lu; Jun Yang; Rui Xu; Min Zhang; Juan Wen; Yelei Wang; Shuo Zhang; Yuanyuan He; Dan Luo; Huazheng Luo; Xingran Zhang (Process Safety and Environmental Protection, 2025)

Numerical investigation on the suction caisson response considering seabed trenches and cyclic loading - Le Wang; Tingran Zhang; Xinglei Cheng; Wanhai Xu; Zhichao Shen; Shengjie Rui; Yinghui Tian (Ocean Engineering, 2025)

Organic matter accumulation driven by land-sea interactions during the Late Cretaceous: A geochemical study of the Nenjiang Formation, Songliao Basin - Congsheng Bian; Shiju Liu; Wei Liu; Xiong Cheng; Xin Liu; Jin Dong; Rui Wang; Yongxin Li; Ming Guan; Qianhui Tian; Wenzhi Zhao (Organic Geochemistry, 2025)

Enhanced CO2 capture performance of N, S co-doped biochar prepared by microwave pyrolysis: Synergistic modulation of microporous structure and functional groups - Jiashan Chen; Junhao Lin; Juan Luo; Zhen Tian; Junshen Zhang; Shichang Sun; Yonglin Shen; Rui Ma (Fuel, 2025)

Energy-saving extractive distillation processes design and optimization for the separation of ethyl acetate and n-heptane azeotrope - Xin Tian; Rui Wang; Honghai Wang; Chunli Li; Jiapeng Liu (Fuel, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Readily recyclable, degradable, stretchable, highly conductive, anti-freezing and anti-drying glycerohydrogel for triboelectric nanogenerator - Sihan Jiang; Yang Wang; Meiqin Tian; Haiyang Zhang; Rui Wang; Haokun Yan; Hao Tan; Rasoul Esmaeely Neisiany; Wei Sun; Zhengwei You (Chemical Engineering Journal, 2025)

A combined strategy of brain neuroprotection and endogenous neuroregeneration for enhanced intracerebral hemorrhage treatment via an injectable biomimetic hydrogel with efficient ROS scavenging and therapeutics delivery - Jiake Xu; Luyao Wan; Xueqi Wang; Yang Wei; Yinhai He; Shenglan You; Rui Zhong; Chengwei Wang; Hao Li; Chao You; Meng Tian (Chemical Engineering Journal, 2025)

Therapeutic Potential of Mesenchymal Stem Cell-Derived Exosomes in Spinal Cord Injury - Jing An; Bo Chen; Rui Zhang; Ding Tian; Kuohao Shi; Lingling Zhang; Gaorong Zhang; Jingchao Wang; Hao Yang (Molecular Neurobiology, 2025)

Insight into the effect of humic acids on transport of Cd2+ in biochar-amended saturated porous media - Tian Zhao; Yongyang Liu; Rui Liu; Fang Wang (Journal of Soils and Sediments, 2025)

A fidelity evaluation model for watermarked vector maps based on improved fuzzy comprehensive evaluation and random forest - Xu Xi; Huimin Tian; Jinglong Du; Mingkang Wu; Rui Huang (Earth Science Informatics, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

The legacy effect of long-term nitrogen fertilization on nitrous oxide emissions - Xue Tian; Huanhuan Wei; Yibai Zhao; Rui Cao; Chong Zhang; Xiaotong Song; Di Wu; Klaus Butterbach-Bahl; Robert M. Rees; Pete Smith; Xiaotang Ju (Science of The Total Environment, 2024)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

Contractor-oriented optimization for wind farm maintenance decision-making considering partial monitoring information and degraded working efficiency - Yifei Wang; Rui He; Zhigang Tian; Yinuo Chen (Ocean Engineering, 2024)

Identification modeling of ship manoeuvring motion based on ISSA-SVR - Rui Tian; Xiufeng Zhang; Xiuwen Liu (Ocean Engineering, 2024)

Contrasting fracturing and cementation timings during shale gas accumulation and preservation: An example from the Wufeng-Longmaxi shales in the Fuling shale gas field, Sichuan Basin, China - Tao Luo; Xiaowen Guo; Zhiliang He; Jian-xin Zhao; Ze Tao; Tian Dong; Rui Yang; Junlin Chen (Marine and Petroleum Geology, 2024)

The role of biofilm in long-term corrosion of cast iron in wastewater reclaim system - Rui An; Juntao Jin; Jun Nan; Yu Tian (Journal of Water Process Engineering, 2024)

Controllable fabrication of high-quantum-yield bimetallic gold/silver nanoclusters as multivariate sensing probe for Hg2+, H2O2, and glutathione based on AIE and peroxidase mimicking activity - Wei Tang; Siqi Chen; Ying Song; Miaomiao Tian; Rui Yan; Baodong Mao; Fang Chai (Journal of Hazardous Materials, 2024)

Ultrabright silicon nanoparticles combined with o-phenylenediamine for ratiometric fluorescence and smartphone imaging dual-mode detection of nitrite - Wen-Jie Gao; Ming-Yue Tian; Xing-Hui Ren; Hao-Rui Zhang; Xi-Wen He; Wen-You Li; Yu-Kui Zhang (Journal of Hazardous Materials, 2024)

Thermodynamic characteristics of nitrifiers reveal the potential NOB inhibition strategies at low temperatures - Ren Li; Lifang Yu; Rui Jiang; Tian Liu; Zhuoya Li; Dangcong Peng (Journal of Cleaner Production, 2024)

Contrastive learning for real SAR image despeckling - Yangtian Fang; Rui Liu; Yini Peng; Jianjun Guan; Duidui Li; Xin Tian (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Instability of natural deep eutectic solvents (NADESs) induced by Amadori rearrangement and its effects on cryopreservation of yeast cells - Rui Hu; Da-Wen Sun; You Tian; Liang Xu; Libin Sun (Food Chemistry, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Development of self-centering and energy-dissipating dual-stage reinforced concrete rocking column-base system - Genqi Xiao; Haishen Wang; Peng Pan; Hengyi Pan; Rui He; Guyu Tian (Engineering Structures, 2024)

Microalgae biofilm barrier to assist the simultaneous nitrogen and phosphorus removal in anammox: Molecular mechanism on sludge granulation and microbial metabolism - Xue Chen; Rui Hu; Mengting Xia; Shiliang Heng; Jiandong Wang; Zhaobin Liu; Jiahua Tian; Xueqin Lu; Guangyin Zhen (Chemical Engineering Journal, 2024)

Microwave pyrolysis of Choerospondias axillaris seeds with their derived biochar for comprehensive utilization of the biomass - Ruolan Zhou; Xiaojie Tian; Xiaofei Wang; Yuan Zeng; Linyao Ke; Qiuhao Wu; Rui Liao; Roger Ruan; Liangliang Fan; Yunpu Wang (Chemical Engineering Journal, 2024)

EGR1 transcriptionally regulates SVEP1 to promote proliferation and migration in human coronary artery smooth muscle cells - Qiang Tian; Jia-He Chen; Yi Ding; Xin-Yu Wang; Jia-Yun Qiu; Qian Cao; Li-Li Zhuang; Rui Jin; Guo-Ping Zhou (Molecular Biology Reports, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

Paleontologic, paleogeographic, and sedimentologic controls on the spatial-temporal distribution of Permian sponge reefs in South China - Xuesong Tian; Kun Liang; Olev Vinn; Dishu Chen; Feng Zhang; Rui Cao; Yue Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Cost-efficient breakthrough: Fabricating multifunctional woven hydrogels from water-soluble polyvinyl alcohol yarn - Chenxing Xiang; Yuanhao Tian; Huiming Ning; Ning Hu; Lidan Zhang; Feng Liu; Rui Zou; Shu Wang; Jie Wen; Leilei Li (Chemical Engineering Journal, 2024)

Rational design of chromium-doped NiFe phosphide/phosphate heterostructures for inhibiting chloride ion adsorption and achieving alkaline seawater splitting at industrial-level current density - Fanjia Sun; Yanhui Wang; Xueqing Tian; Rui Zhu; Ziliang Zhuang; Youbin Zheng; Jianbing Zang; Liang Dong (Chemical Engineering Journal, 2024)

High density cobalt single atom catalysts for H2O2 electrosynthesis: A critical design of carbon nitride skeleton - Zhe Xue; Rui Tan; Jinzhong Tian; Hua Hou; Xinyu Zhang; Yuhong Zhao (Chemical Engineering Journal, 2024)

Elevating electrochemical performance of Na4MnCr(PO4)3 cathode material for sodium ion batteries through the synergistic effect of Sc doping and RuO2/C coating - Qing Zhu; Jinxin Wu; Rui Tong; Xiuli Hu; Ningchen Tian; Botian Liu; Jiqiong Jiang; Yanwei Li; Jianwen Yang; Jianwei Zhao (Chemical Engineering Journal, 2024)

Hybrid packed bed bioreactor using combined biodegradation and ozonation to enhance nitrogen and micropollutants removal from landfill leachate - Xuetong Yang; Ze Liu; Changtao Chen; Tao Zhang; Qintong Wang; Rui Zhang; Feng Duan; Xiang Tian; Mingshui Yao; Kristof Demeestere; Stijn W.H. Van Hulle (Bioresource Technology, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Specific and Plastic: Chandelier Cell-to-Axon Initial Segment Connections in Shaping Functional Cortical Network - Yanqing Qi; Rui Zhao; Jifeng Tian; Jiangteng Lu; Miao He; Yilin Tai (Neuroscience Bulletin, 2024)
Axon initial segment (AIS) is the most excitable subcellular domain of a neuron for action potential initiation. AISs of cortical projection neurons (PNs) receive GABAergic synaptic inputs primarily from chandelier cells (ChCs), which are believed to regulate action potential generation and modulate neuronal excitability. As individual ChCs often innervate hundreds of PNs, they may alter the activity of PN ensembles and even impact the entire neural network. During postnatal development or in response to changes in network activity, the AISs and axo-axonic synapses undergo dynamic structural and functional changes that underlie the wiring, refinement, and adaptation of cortical microcircuits. Here we briefly introduce the history of ChCs and review recent research advances employing modern genetic and molecular tools. Special attention will be attributed to the plasticity of the AIS and the ChC-PN connections, which play a pivotal role in shaping the dynamic network under both physiological and pathological conditions.

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Weights embedding Informer prediction algorithm-based fault diagnosis framework for nuclear power plant - Tan Canyi; Zheng Wei; Wang Bo; Tan Sichao; Liang Biao; Li Jiangkuan; Han Rui; Ke Zhiwu; Tian Ruifeng (Annals of Nuclear Energy, 2024)

Flow Field Analysis and Development of a Prediction Model Based on Deep Learning - Yingjie Yu; Xiufeng Zhang; Lucai Wang; Rui Tian; Xiaobin Qian; Dongdong Guo; Yanwei Liu (Journal of Marine Science and Engineering, 2024)
The velocity of ocean currents significantly affects the trajectory prediction of ocean drifters and the safe navigation of intelligent vessels. Currently, most ocean current predictions focus on time-based forecasts at specific fixed points. In this study, deep learning based on the flow field prediction model (CNNs–MHA–BiLSTMs) is proposed, which predicts the changes in ocean currents by learning from historical flow fields. Unlike conventional models that focus on single-point current velocity data, the CNNs–MHA–BiLSTMs model focuses on the ocean surface current information within a specific area. The CNNs–MHA–BiLSTMs model integrates multiple convolutional neural networks (CNNs) in parallel, multi-head attention (MHA), and bidirectional long short-term memory networks (BiLSTMs). The model demonstrated exceptional modelling capabilities in handling spatiotemporal features. The proposed model was validated by comparing its predictions with those predicted by the MIKE21 flow model of the ocean area within proximity to Dalian Port (which used a commercial numerical model), as well as those predicted by other deep learning algorithms. The results showed that the model offers significant advantages and efficiency in simulating and predicting ocean surface currents. Moreover, the accuracy of regional flow field prediction improved with an increase in the number of sampling points used for training. The proposed CNNs–MHA–BiLSTMs model can provide theoretical support for maritime search and rescue, the control or path planning of Unmanned Surface Vehicles (USVs), as well as protecting offshore structures in the future.

Response of soil quality degradation to cultivation and soil erosion: A case study in a Mollisol region of Northeast China - Rui Ma; Zhiyuan Tian; Yan Zhao; Yihang Wu; Yin Liang (Soil and Tillage Research, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Iron-based materials for immobilization of heavy metals in contaminated soils: A critical review - Yaxin Tian; Guangfei Qu; Rui Xu; Xinxin Liu; Caiyue Jin (Journal of Environmental Chemical Engineering, 2024)

Thermo-economic analysis and multi-objective optimization of cryogenic CO2 capture systems based on liquefied natural gas cold energy utilization - Gequn Shu; Borui Liu; Hua Tian; Ligeng Li; Rui Sun; Xuan Wang (Journal of Environmental Chemical Engineering, 2024)

CO2 retention in high-pressure/high-temperature reservoirs of the Yinggehai Basin, northwestern South China Sea - Jinyan Lin; Rui Liu; Niklas Heinemann; Johannes M. Miocic; Jinqiang Tian; Zengyu Chen; Lin Hu; Yazhen Zhang; Julien Amalberti; Lichao Wang (International Journal of Greenhouse Gas Control, 2024)

Developing a radio frequency-hot air spouting treatment for efficient dehydration of carrot cubes: Evaluation of the heating and moisture distribution uniformity - Junjie Zheng; Xin Ye; Longlong Jiang; Xiaojiang Wang; Mengge Li; Yingqi Tian; Rui Li; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Sunflower-YOLO: Detection of sunflower capitula in UAV remote sensing images - Rui Jing; Qinglin Niu; Yuyu Tian; Heng Zhang; Qingqing Zhao; Zongpeng Li; Xinguo Zhou; Dongwei Li (European Journal of Agronomy, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Evolutionary dynamics of cooperation coupled with ecological feedback compensation - Zi-Xuan Guo; Tian-Jiao Feng; Yi Tao; Rui-Wu Wang; Xiu-Deng Zheng (BioSystems, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

Soil urease functional stability to Hg pollution: An ecotoxicological perspective - Hui Huang; Haixia Tian; Yan Li; Ziquan Wang; Tiantian Yang; Rui Qian; Mallavarapu Megharaj; Wenxiang He (Ecotoxicology, 2024)

Structure and Evolution of Multi-Trend Faults in BZ19-6 Buried Hill of the Bohai Bay Basin, Eastern China - Rui Lou; Yonghe Sun; Fujie Jiang; Yumin Liu; Tian Gao (Journal of Marine Science and Engineering, 2024)
Defining the structure and evolution of multi-trend faults is critical for analyzing the accumulation of hydrocarbons in buried hills. Based on high-resolution seismic and drilling data, the structural characteristics and evolutionary mechanism of multi-trend faults were investigated in detail through the structural analysis theory and quantitative calculations of fault activity, allowing us to determine the implication that fault evolution exerts on hydrocarbon accumulation in the BZ19-6 buried hill. There are four kinds of strike faults developed on the buried hill: SN-, NNE-, NE–ENE-, and nearly EW-trending, which experienced the Mesozoic Indosinian, Yanshan, and Cenozoic Himalayan tectonic movements. During the Indosinian, the BZ19-6 was in a SN-oriented compressional setting, with active faults composed of SN-trending strike-slip faults (west branch of the Tanlu fault zone) and near EW-trending thrust faults (Zhang-peng fault zone). During the Yanshanian, the NNE-trending normal faults were formed under the WNW–ESE tensile stress field. Since the Himalayan period, the BZ19-6 buried hill has evolved into the rifting stage. In rifting stage Ⅰ, all of the multi-trend pre-existing faults were reactivated, and the EW-trending thrust faults became normal faults due to negative inversion. In rifting stage II, a large number of NE–ENE-trending normal faults were newly formed in the NW–SE-oriented extensional setting, which made the structure pattern more complicated. In rifting stage III, the buried hill entered the post-rift stage, with only part of the NNE- and NE–ENE-trending faults continuously active. Multi-trend faults are the result of the combination of various multi-phase stress fields and pre-existing structures, which have great influence on the formation of tectonic fractures and then control the distribution of high-quality reservoirs in buried hills. The fractures controlled by the NNE- and EW-trending faults have higher density and scale, and fractures controlled by NE–ENE trending faults have stronger connectivity and effectiveness. The superposition of multi-trend faults is the favorable distribution of high-quality reservoirs and the favorable accumulation area of hydrocarbon.

Crop aboveground biomass monitoring model based on UAV spectral index reconstruction and Bayesian model averaging: A case study of film-mulched wheat and maize - Zhikai Cheng; Xiaobo Gu; Zhihui Zhou; Rui Yin; Xiaobo Zheng; Wenlong Li; Wenjing Cai; Tian Chang; Yadan Du (Computers and Electronics in Agriculture, 2024)

Green natural deep eutectic agents (GNDEAs) for biocryopreservation: Syntheses, properties and advanced applications - Rui Hu; Da-Wen Sun; You Tian (Trends in Food Science & Technology, 2024)

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

A novel method of fuel consumption prediction for wing-diesel hybrid ships based on high-dimensional feature selection and improved blending ensemble learning method - Tian Lan; Lianzhong Huang; Ranqi Ma; Zhang Ruan; Shan Ma; Zhongwei Li; Haoyang Zhao; Cong Wang; Rui Zhang; Kai Wang (Ocean Engineering, 2024)

Construction of an S-scheme electron transfer channel in Cu0/CuFe2O4 magnetic plate column reactor for the LEV degradation: New strategy of visible Photo-Fenton system application - Rui Wang; Aiwen Wang; Yunhao Pan; Jiaxin Ni; Yingjie Deng; Zhe Tao; Xiongying Liang; Jingrui Tang; Xunming Tian; Tiancheng Zha; Dongmei Liu; Jun Ma (Journal of Hazardous Materials, 2024)

Propane dehydrogenation performance of titanosilicate-1 supported CoOx catalysts by adjusting the acidity and reducibility - Xue Cai; Yongzheng Zhao; Lili Cai; Xiaoyan Tian; Cunzi Wei; Dandan Qin; Meitong Li; Rui Tao; Wenling Chu; Weishen Yang (Fuel, 2024)

Decoding polyphenol metabolism in patients with Crohn’s disease: Insights from diet, gut microbiota, and metabolites - Liyuan Xiang; Shuyu Zhuo; Wanrong Luo; Chunyang Tian; Shu Xu; Xiaozhi Li; Yijun Zhu; Rui Feng; Minhu Chen (Food Research International, 2024)

Bifunctional halloysite nanotube-based Ripk1 siRNA delivery system rescues cognitive impairment by targeting amyloid β plaques for clearance and reducing necrotic neurons in Alzheimer’s disease mice - Linmei Wu; Shuo Tan; Yizhu Yan; Lianghao Zhu; Zhaoyuan Wu; Zhihong Liu; Qiang Cheng; Qiuhao Qu; Xinyu Li; Qi Zhang; Jiayi Liu; Jun Chang; et al. (Chemical Engineering Journal, 2024)

A fully degradable flexible membrane via green synthesis for highly effective separation of oil-water emulsions - Yunhao Pan; Tiancheng Zha; Xunming Tian; Liuqian An; Aiwen Wang; Rui Wang; Yibo Zhang; Jinxin Yao; Dongmei Liu; Shouzhu Li; Wei Wang (Chemical Engineering Journal, 2024)

Outdoor tubular photobioreactor microalgae-microorganisms biofilm treatment of municipal wastewater: Enhanced heterotrophic assimilation and synergistic aerobic denitrogenation - Pan Li; Yajun Luo; Jiansong Tian; Yiwei Cheng; Shiji Wang; Xin An; Jingxian Zheng; Heng Yan; Hongtao Duan; Jin Zhang; Zhicheng Pan; Yangwu Chen; et al. (Bioresource Technology, 2024)

Progressive Freezing-Melting Method for Removal Boron from Simulated Seawater - Yihong Zou; Yan Zhang; Chen Zhao; Rui Mei; Lin Lin; Chunbo Liu; Yucan Liu; Yepeng Tian; Futian Chen (Water, Air, & Soil Pollution, 2024)

Shoot and Root Traits are Associated with Varying Soil Phosphorus Supply in Chinese Cabbage - Hou Sai-sai; Pu Zi-tian; Zhang Rui-fang; Zhang Chi; Wang Hong; Wang Xin-xin; Zhao Jian-jun (Journal of Soil Science and Plant Nutrition, 2024)

Metformin improves cognitive dysfunction through SIRT1/NLRP3 pathway–mediated neuroinflammation in db/db mice - Tian Hu; Jun-Wen Wei; Jia-Yi Zheng; Qing-Yi Luo; Xin-Rui Hu; Qun Du; Ye-Feng Cai; Shi-Jie Zhang (Journal of Molecular Medicine, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

PET microplastics influenced microbial community and heavy metal speciation in heavy-metal contaminated soils - Yajuan Tang; Yi Xing; Xin Wang; Haobo Ya; Tian Zhang; Mingjie Lv; Jianchao Wang; Han Zhang; Wei Dai; Duo Zhang; Rui Zheng; Bo Jiang (Applied Soil Ecology, 2024)

MARCH1 and MARCH2 inhibit pseudorabies virus replication by trapping the viral cell-to-cell fusion complex in trans-Golgi network - Rui Huang; Cui-Hong Rao; Yuan-Zhe Bai; Changqing Yu; Meng Chen; Jin-Mei Peng; Shi-Jia Xu; Yue Sun; Meng Fandan; Chuang Lyu; Mirwaise Khan; Tong-Qing An; et al. (Veterinary Microbiology, 2024)

Effect of tunnel ventilation on surrounding rock temperature field and heat regulating circle during construction phase - Ming-Rui Luo; Yu-Chun Tao; Zuo-Bing Yuan; Liang-Liang Tao; Chuan He; Yan-Ping Yuan; Xiao- Yu Tian; Yan-Hua Zeng (Tunnelling and Underground Space Technology, 2024)

Developing a spouted bed for combined radio frequency-hot air treatments to improve the heating uniformity in high-moisture carrot cubes - Junjie Zheng; Longlong Jiang; Xin Ye; Xiaojiang Wang; Yingqi Tian; Mengge Li; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Effect of BaTiO3 as a filling material with adjustable dielectric properties on improving the radio frequency heating uniformity in red jujubes - Longlong Jiang; Junjie Zheng; Mengge Li; Yingqi Tian; Xiaojiang Wang; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Developing effective radio frequency drying processes for tiger nuts: Dynamic analysis of moisture state, dielectric properties and quality - Mengge Li; Yingqi Tian; Longlong Jiang; Juanjuan Xu; Rui Li; Shaojin Wang (Journal of Food Engineering, 2024)

Extended applications of the small-scale radio frequency system for improving the heating performance of multi-component rice - Yingqi Tian; Haibo Yu; Mengge Li; Longlong Jiang; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2024)

Polydatin: a potential NAFLD therapeutic drug that regulates mitochondrial autophagy through SIRT3-FOXO3-BNIP3 and PINK1-PRKN mechanisms - a network pharmacology and experimental investigation - Jing He; Yi-cai Qian; Ying-chuan Yin; Jing-rui Kang; Tian-rong Pan (Chemico-Biological Interactions, 2024)

Engineering disease-resistant plants with alternative translation efficiency by switching uORF types through CRISPR - Jingjing Tian; Zhijuan Tang; Ruixia Niu; Yulu Zhou; Dan Yang; Dan Chen; Ming Luo; Rui Mou; Meng Yuan; Guoyong Xu (Science China Life Sciences, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

A highly sensitive and colorimetric fluorescent probe for visualizing hydroxylamine in immune cells - Wei Du; Yang Tian; Yu-An Feng; Xiao-Wei Cong; Rui Tan; Ya-Wen Wang; Yu Peng (Analytica Chimica Acta, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Fabrication of versatile Fe3O4/GO/Au composite nanomaterial as SERS-active substrate for detection of pesticide residue - Rui Wu; Xi Song; Guanghui Tian (Environmental Science and Pollution Research, 2024)

A review of distribution and functions of extracellular DNA in the environment and wastewater treatment systems - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Bo Zhang (Chemosphere, 2024)

Effect of volatile compounds produced by Weissella cibaria BWL4 on Botrytis cinerea infection in fruit and complete genome sequence analysis of BWL4 - Danfeng Zhang; Xuehua Xu; Xinrui Tian; Rui Wang; Tingting Hu; Wei Shi; Wanling Bi; Yingwang Ye (Postharvest Biology and Technology, 2024)

Different reference genomes determine different results: Comparing SNP calling in RAD-seq of Engelhardia roxburghiana using different reference genomes - Pei-Han Huang; Tian-Rui Wang; Min Li; Ou-Yan Fang; Ren-Ping Su; Hong-Hu Meng; Yi-Gang Song; Jie Li (Plant Science, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

YOLOv5-T: A precise real-time detection method for maize tassels based on UAV low altitude remote sensing images - Rui Gao; Yishu Jin; Xin Tian; Zheng Ma; Siqi Liu; Zhongbin Su (Computers and Electronics in Agriculture, 2024)

Qualitative classification of waste garments for textile recycling based on machine vision and attention mechanisms - Rui Tian; Ziqi Lv; Yuhan Fan; Tianyu Wang; Meijie Sun; Zhiqiang Xu (Waste Management, 2024)

Cadmium pollution exacerbated by drought: Insights from the nanoscale interaction at the clay mineral surface - Guantong Tian; Qi Luo; Rui Xing; Jianguo Zhang; Xiong Li (Science of The Total Environment, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Comparative steroidogenic effects of hexafluoropropylene oxide trimer acid (HFPO-TA) and perfluorooctanoic acid (PFOA): Regulation of histone modifications - Fuping Li; Rui Yang; Lu Lu; Weizhen Hua; Yan Sun; Meiping Tian; Yanyang Lu; Qingyu Huang (Environmental Pollution, 2024)

Exploiting excavation-induced displacement for slope heterogeneity characterization and stability analysis - Jing-Sen Cai; Tian-Chyi Jim Yeh; E-Chuan Yan; Rui-Xuan Tang (Computers and Geotechnics, 2024)

Stretchable ionogels: Recent advances in design, toughening mechanisms, material properties and wearable devices applications - Caiyue Huang; Xiaohua Jia; Ding Wang; Xisheng Sun; Qi Liang; Rui Tian; Liyuan Guo; Jin Yang; Haojie Song (Chemical Engineering Journal, 2024)

Efficient acidic CO2 electroreduction to formic acid by modulating electrode structure at industrial-level current - Zhenhui Wang; Hongdong Li; Tian Dong; Yanling Geng; Xiaofeng Tian; Rui Chang; Jianping Lai; Shouhua Feng; Lei Wang (Chemical Engineering Journal, 2024)

Chitosan-based injectable hydrogel with multifunction for wound healing: A critical review - Aiqin Li; Bin Ma; Shiyao Hua; Rui Ping; Lu Ding; Bingren Tian; Xu Zhang (Carbohydrate Polymers, 2024)

Calmodulin Gene of Blunt Snout Bream (Megalobrama amblycephala): Molecular Characterization and Differential Expression after Aeromonas hydrophila and Cadmium Challenges - Jinwei Gao; Hao Wu; Xing Tian; Jiayu Wu; Min Xie; Zhenzhen Xiong; Dongsheng Ou; Zhonggui Xie; Rui Song (Fishes, 2024)
Calmodulin (Calm), a crucial Ca2+ sensor, plays an important role in calcium-dependent signal transduction cascades. However, the expression and the relevance of Calm in stress and immune response have not been characterized in Megalobrama amblycephala. In this study, we identified the full-length cDNA of Calm (termed MaCalm) in blunt snout bream M. amblycephala, and analyzed MaCalm expression patterns in response to cadmium and Aeromonas hydrophila challenges. MaCalm was 1603 bp long, including a 5′-terminal untranslated region (UTR) of 97 bp, a 3′-terminal UTR of 1056 bp and an open reading frame (ORF) of 450 bp encoding a polypeptide of 149 amino acids with a calculated molecular weight (MW) of 16.84 kDa and an isoelectric point (pI) of 4.09. Usually, MaCalm contains four conservative EF hand motifs. The phylogenetic tree analysis indicated that the nucleotide sequence of MaCalm specifically clustered with Ctenopharyngodon idella with high identity (98.33%). Tissue distribution analysis demonstrated that the ubiquitous expression of MaCalm mRNA was found in all tested tissues, with the highest expression in the brain and the lowest expression in muscle. MaCalm showed significant upregulation at 14 d and 28 d post exposure to varying concentrations of cadmium in the liver; HSP70 transcripts in the liver significantly upregulated at 14 d post exposure to different concentrations of cadmium. Moreover, in response to the A. hydrophila challenge in vivo, MaCalm transcripts in the liver first increased and then decreased, but MaCalm transcripts in the kidney declined gradually with prolonged infection. After the A. hydrophila challenge, the expression level of HSP70 was significantly downregulated at 24 h in the liver and its expression level was notably downregulated at 12 h and at 24 h in the kidney. Collectively, our results suggest that MaCalm possesses vital roles in stress and immune response in M. amblycephala.

Establishment, characterization and application of Largemouth bronze gudgeon (Coreius guichenoti) fin and skin cell lines in disease resistance - Qi Zhang; Zhihong Gong; Rui Shi; Yuhong Shi; Chenfei Guo; Xiaolin Liao; Hua Tian; Na Wang (Aquaculture, 2024)

Assessing ammonium pollution and mitigation measures through a modified watershed non-point source model - Feng Han; Qing Tian; Nengwang Chen; Zhaoping Hu; Yao Wang; Rui Xiong; Peng Xu; Wei Liu; Alejandra Stehr; Ricardo O. Barra; Yi Zheng (Water Research, 2024)

Insights into the generation of multiple reactive species in UV254/PMS/I− system and their roles for degradation of phenolic and non-phenolic pollutants - Zhen Tian; Yiyang Li; Lina Wang; Rui Xu; Aihua Wei; Jun He; Chengjun Wang (Journal of Water Process Engineering, 2024)

Experimental study and model optimization of thermodynamic performance of a single screw water vapor compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Yanan Li; Li Wang; Xia Guo; Rui Tian; Mingxin He; Chongguang Gao (International Journal of Refrigeration, 2024)

Constructing composite active centers optimized with Cr-doped NiS/NiS2 heterostructure for efficiently catalyzing alkaline hydrogen evolution reaction - Fanjia Sun; Xueqing Tian; Jianbing Zang; Rui Zhu; Zhiwei Hou; Youbin Zheng; Yanhui Wang; Liang Dong (Fuel, 2024)

Evolution and mechanism of impedance in PEMFC induced by cathode ammonia contamination - Yuan Jing; Jiayin Tian; Xin Cai; Rui Lin (Fuel, 2024)

Dual-bioinspired and ultra-flexible photothermal eutectogels for highly efficient passive anti-freezing - You Tian; Da-Wen Sun; Liang Xu; Libin Sun; Rui Hu (Chemical Engineering Journal, 2024)

Enhanced peroxymonosulfate activation for degradation of iodinated contrast media by microwave-induced bimetallic carbon-based catalysts: Insight into the synergistic mechanism between microwaves and bimetallic sites - Zixia He; Zhen Tian; Juan Luo; Shichang Sun; Guopeng Zhu; Rui Ma (Chemical Engineering Journal, 2024)

Highly thermally conductive composites with boron nitride nanoribbon array - Peng Wei; Lei Feng; Qiang Chen; Zhijie Dong; Qiang Song; Rui Tian; Ruoxi Zhang; Liyuan Guo; Dongfang Xu; Mengdan Hou; Haojie Song (Chemical Engineering Journal, 2024)

Circular RNA MKLN1 promotes epithelial-mesenchymal transition in pulmonary fibrosis by regulating the miR-26a/b-5p/CDK8 axis in human alveolar epithelial cells and mice models - Yong Zhu; Xiaoxiao Meng; Xian Zhu; Jiaxiang Zhang; Hui lv; Feiyao Wang; Jinfeng Wang; Cheng Chen; Mengting Chen; Dapeng Wang; Wei Jin; Rui Tian; et al. (Archives of Toxicology, 2024)
Pulmonary fibrosis involves destruction of the lung parenchyma and extracellular matrix deposition. Effective treatments for pulmonary fibrosis are lacking and its pathogenesis is still unclear. Studies have found that epithelial-mesenchymal transition (EMT) of alveolar epithelial cells (AECs) plays an important role in progression of pulmonary fibrosis. Thus, an in-depth exploration of its mechanism might identify new therapeutic targets. In this study, we revealed that a novel circular RNA, MKLN1 (circMKLN1), was significantly elevated in two pulmonary fibrosis models (intraperitoneally with PQ, 50 mg/kg for 7 days, and intratracheally with BLM, 5 mg/kg for 28 days). Additionally, circMKLN1 was positively correlated with the severity of pulmonary fibrosis. Inhibition of circMKLN1 expression significantly reduced collagen deposition and inhibited EMT in AECs. EMT was aggravated after circMKLN1 overexpression in AECs. MiR-26a-5p/miR-26b-5p (miR-26a/b), the targets of circMKLN1, were confirmed by luciferase reporter assays. CircMKLN1 inhibition elevated miR-26a/b expression. Significantly decreased expression of CDK8 (one of the miR-26a/b targets) was observed after inhibition of circMKLN1. EMT was exacerbated again, and CDK8 expression was significantly increased after circMKLN1 inhibition and cotransfection of miR-26a/b inhibitors in AECs. Our research indicated that circMKLN1 promoted CDK8 expression through sponge adsorption of miR-26a/b, which regulates EMT and pulmonary fibrosis. This study provides a theoretical basis for finding new targets or biomarkers in pulmonary fibrosis.

ARHGEF18 can promote BVDV NS5B activation of the host NF-κB signaling pathway by combining with the NS5B-palm domain - Jiying Yin; Naichao Diao; Tian Tian; Qi Wang; Shuqi Ma; Ning He; Hongming Zhou; Zehui Zhou; Wenyi Jia; Xiaonan Wang; Kun Shi; Rui Du (Veterinary Microbiology, 2024)

Isolation of Prunus persica kernel protein and its physicochemical properties and aggregating performance modulated by heating and ultrasonication - Chunxiao Tao; Taiwei Ye; Dongyun Tang; Rui Tian; Yan Xie (Sustainable Chemistry and Pharmacy, 2024)

Rapid immobilization of arsenic in contaminated soils by microwave irradiation combined with magnetic biochar: Microwave-induced electron transfer for oxidation and immobilization of arsenic (III) - Dengcai Zhang; Junhao Lin; Juan Luo; Shichang Sun; Xi Zhang; Rui Ma; Juan Peng; Fei Ji; Shuaifei Zheng; Zhen Tian; Ning Ma (Science of The Total Environment, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Arbuscular mycorrhizal fungi reduce ammonia emissions under different land-use types in agro-pastoral areas - Huaisong WANG; Rui GUO; Yibo TIAN; Nan CUI; Xinxin WANG; Lei WANG; Zhongbao YANG; Shuying LI; Jixun GUO; Lianxuan SHI; Tao ZHANG (Pedosphere, 2024)

Asymmetric response of transition metal cationic orbitals to applied electric field - Xinmin Liu; Wanglin Chen; Ying Tang; Shuang Xiao; Qinyi Li; Wuquan Ding; Laosheng Wu; Rui Tian; Rui Li; Hang Li (Journal of Hazardous Materials, 2024)

Enhanced tough recyclable hemiaminal dynamic covalent network with boron nitride composites material with high thermal conductivity at low filler content - Caiyue Huang; Xiaohua Jia; Rui Tian; Jin Yang; Haojie Song (Journal of Cleaner Production, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Synergistic removal of sulphur-containing malodourous gases via peroxydisulfate activation in three-dimensional electrode system - Rui Luo; Shugen Liu; Chen Li; Xiaofeng Huang; Ping Ning; Senlin Tian (Journal of Environmental Chemical Engineering, 2024)

Multi-hazard stochastic response analysis and reliability evaluation of a 5 MW monopile offshore wind turbine based on extended platform FAST-S - Yazhou Xu; Rui Tian; Jing Duan; Yanqiong Ding; Hui Zhang (Engineering Structures, 2024)

A modified Chebyshev collocation method for the generalized probability density evolution equation - Rui Tian; Yazhou Xu (Engineering Structures, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Self-enhanced nanohydrogel electrochemiluminescence biosensor based on CRISPR/Cas12a and gold platinum nanoparticles modification for high-sensitivity detection of Burkholderia pseudomallei - Yuexin Wang; Bo Shen; Nini Luo; Cai Li; Haiping Wu; Yanshuang Wang; Shen Tian; Xuemiao Li; Rui Liu; Xinmin Li; Junman Chen; Wei Cheng; et al. (Chemical Engineering Journal, 2024)

Hollow AMn2O4-δ (A = Co, Zn, Ni) nanotube for direct photo-oxidation of methane to C1 and C2 alcohols at atmospheric pressure and room temperature - Jun Duan; Shiying Fan; Xinyong Li; Jing Wang; Chunpeng Bai; Shixuan Yu; Weitong Ling; Rui Tian; Dongke Zhang (Chemical Engineering Journal, 2024)

Impacts of an upper tropospheric cold low on the extreme precipitation in Henan Province, China in July 2021 - Liangliang Li; Wenshou Tian; Jian Li; Jinlong Huang; Rui Wang; Jiali Luo (Atmospheric Research, 2024)

Analysis of landslide deformation in eastern Qinghai Province, Northwest China, using SBAS-InSAR - Haibo Tian; Pinglang Kou; Qiang Xu; Yuxiang Tao; Zhao Jin; Ying Xia; Jiangfan Feng; Rui Liu; Yongcheng Gou (Natural Hazards, 2024)

A real-time constellation image classification method of wireless communication signals based on the lightweight network MobileViT - Qinghe Zheng; Sergio Saponara; Xinyu Tian; Zhiguo Yu; Abdussalam Elhanashi; Rui Yu (Cognitive Neurodynamics, 2024)

Cement kiln geared up to dispose industrial hazardous wastes of megacity under industrial symbiosis - Kailingli Liao; Zeshi Feng; Jin Wu; He Liang; Yuhan Wang; Wenfei Zeng; Yichun Wang; Jinping Tian; Rui Liu; Lyujun Chen (Resources, Conservation and Recycling, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

The transmission of isotopic signals from precipitation to groundwater and its controls: An experimental study with soil cylinders of various soil textures and burial depths in a monsoon region - Ying Jiang; Jie Li; Rui Zuo; Congjian Sun; Yuanzheng Zhai; Lijun Tian; Wei Dai; Shufang Wang; Ziqi Shang; Yulian Liu; Xuan Jiao; Yuxi Xie; et al. (Journal of Hydrology, 2024)

A high-affinity fluorescent probe for human uridine-disphosphate glucuronosyltransferase 1A9 function monitoring under environmental pollutant exposure - Yi-Sheng Miao; Jia-Yue Wang; Rui-Rui Zhuang; Xiao-Kui Huo; Zi-Chang Yi; Xiao-Nan Sun; Zhen-Long Yu; Xiang-Ge Tian; Jing Ning; Lei Feng; Xiao-Chi Ma; Xia Lv (Journal of Hazardous Materials, 2024)

Quantitative health risk assessment of microbial hazards from water sources for community and self-supply drinking water systems - Cheng Yan; Wei-di Wan; Rui-ning Wang; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zaheer Ahmad Nasir; Frederic Coulon (Journal of Hazardous Materials, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Realizing synergy between pollution reduction and carbon mitigation in industrial parks: From model development to tool application - Yizheng Lyu; Lujun Chen; Jinping Tian; Rui Liu; Quan Zhou (Journal of Cleaner Production, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

Modulation of charge distribution enabling CuNi nano-alloys for efficient ammonia oxidation reaction to nitrite production - Zixian Mao; Yunrui Tian; Baitong Guo; Rui Chen; Ye Zeng; Feng Hou; Xiao Yan; Ji Liang (Chemical Engineering Journal, 2024)

ZIF-8 Gel/PIM-1 mixed matrix membranes for enhanced H2/CH4 separations - Keming Zhang; Xianye Luo; Sihui Li; Xiaohe Tian; Qingnan Wang; Chenlu Liu; Yanting Tang; Xiaoting Feng; Rui Zhang; Shuangfeng Yin; Shaofei Wang (Chemical Engineering Journal, 2024)

Covalent-Metal organic Frameworks: Preparation and applications - Zhaobo Wang; Chen Wang; Qiming Hu; Xuefei Lei; Rui Guo; Junhua You; Ye Tian; Fan Yang; Meili Lv (Chemical Engineering Journal, 2024)

An efficient synthesis and organic-modification coupling strategy to produce highly dispersed ultrathin antioxidant intercalated layered double hydroxides for enhancing performance of polypropylene composites - Zijia Li; Menghua Zhao; Rui Tian; Yalin Shi; Weiliang Tian; Yiqing Bai; Meng Xu; Kai Xu; Dali Gao; Yongjun Feng (Chemical Engineering Journal, 2024)

A particle-scale insight into the face stability of shallow EPB shield tunnels in dry cobble-rich soil - Jun Wang; Guojin Lin; Rui Tang; Yan Zhang; Zhigang Yao; Kun Feng; Ning Tian; Ziquan Chen; Chuan He (Tunnelling and Underground Space Technology, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Molecular epidemiology, phenotypic and genomic characterization of antibiotic-resistant enterococcal isolates from diverse farm animals in Xinjiang, China - Wanzhao Chen; Qiaojun Wang; Huimin Wu; Panpan Xia; Rui Tian; Ruichao Li; Lining Xia (Science of The Total Environment, 2024)

Vapor-liquid equilibrium measurement for carbon dioxide (CO2)+propylene (R1270) binary mixture at temperatures from subcritical to supercritical - Zirui Wu; Rui Sun; Lingfeng Shi; Peng Hu; Hua Tian; Xuan Wang; Gequn Shu (International Journal of Refrigeration, 2024)

Involvement of TLRs/NF-κB/ESE-1 signaling pathway in T-2 toxin-induced cartilage matrix degradation - Yawen Shi; Rui Wang; Yanan Li; Yixin Cui; Ying He; Hui Wang; Yinan Liu; Meng Zhang; Yonghui Chen; Mingzhao Jia; Kunpan Chen; Xingran Ruan; et al. (Environmental Pollution, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

In-depth insight into improvement of simultaneous nitrification and denitrification/biofouling control by increasing sludge concentration in membrane reactor: performance, microbial assembly and metagenomic analysis - Rui Huang; Mingyue Geng; Shanshan Gao; Xing Yin; Jiayu Tian (Bioresource Technology, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

Polarization induced covalent/hydrogen bonding adsorption of NH4+ and K+ in soils: comparison study on permanently and variably charged soils - Dian Liu; Rui Tian; Xinmin Liu; Hang Li (Journal of Soils and Sediments, 2024)

Local dynamic update methods for 3D geological body structure model and voxel model - Yiping Tian; Shengkun Xiao; Rui Zhang; Zhengping Weng; Xuechao Wu; Yongjin Wu (Earth Science Informatics, 2024)

Dynamic Effect of Landslides Triggered by Earthquake: A Case Study in Moxi Town of Luding County, China - Hongfu Zhou; Fei Ye; Wenxi Fu; Bin Liu; Tian Fang; Rui Li (Journal of Earth Science, 2024)

Structural elucidation of a non-starch polysaccharides from Lilii Bulbus and its protective effects against corticosterone-induced neurotoxicity in PC12 cells - Yili Zheng; Xueying Li; Danna Lin; Jian Wu; Yufei Tian; Hongyuan Chen; Wen Rui (Glycoconjugate Journal, 2024)

New 4',5'-methylenedioxyflavone derivatives from the whole plant of sarcandra glabra - Ya-Qiu Qin; Wei Liu; Rui Yin; Ping-Ting Xiao; Zi-Yuan Wang; Tian-Qing Huang; E-Hu Liu (Natural Product Research, 2024)

Stytontriterpenes A−C, three unusual oleanane-derived triterpenoids from the resin of Styrax tonkinensis as potential immunosuppressive agents in atherosclerosis - Rui-Yan Jiang; Ling-Wen Yao; Yin-Hong Lv; Zhong-Tian Guo; Fei-Fei Wang; Hong-Hua Cui; Yuan-Yuan Cheng; Feng Wang (Phytochemistry, 2024)

Revealing the membrane fouling behavior and interfacial interaction mechanism in a combined visible light photocatalysis-ultrafiltration system for advanced purification of NOM - Rui Yu; Yanling Yang; Liping Tian; Xing Li; Chunjiao Liu; Tianjie Sun; Haiqing Chang; Zhiwei Zhou (Journal of Water Process Engineering, 2024)

Source characteristics of polycyclic aromatic hydrocarbons and polychlorinated biphenyls in surface soils of Shenyang, China: A comparison of two receptor models combined with Monte Carlo simulation - Yiran Li; Fulin Tian; Rui Zhong; Haibo Zhao (Journal of Hazardous Materials, 2024)

A review of the strategy to promote microalgae value in CO2 conversion-lipid enrichment-biodiesel production - Huan Liu; Tian-Ji Liu; Hua-Wei Guo; Ya-Jun Wang; Rui Ji; Le-Le Kang; Yi-Tong Wang; Xuan Guo; Jun-Guo Li; Li-Qun Jiang; Zhen Fang (Journal of Cleaner Production, 2024)

LED-driven photocatalytic degradation of tetracycline by chromite ore processing residue (COPR): Mechanism, pathway, toxicity assessment - Shuo Zhang; Cunfang Lu; Yelei Wang; Cheng Tian; Peng Chen; Mingyuan Yang; Min Zhang; Rui Xu; Yuanyuan He; Zilong Li (Journal of Cleaner Production, 2024)

Fluid evolution and gas enrichment in the Wufeng-Longmaxi shale reservoirs of the eastern Sichuan Basin, SW China - Tao Luo; Xiaowen Guo; Zhiliang He; Tian Dong; Ze Tao; Rui Yang; Keqing Wang (Journal of Asian Earth Sciences, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)

Ultra-stretchable, sensitive and breathable electronic skin based on TPU electrospinning fibrous membrane with microcrack structure for human motion monitoring and self-powered application - Yu Tian; Mengjie Huang; Yalong Wang; Yanjun Zheng; Rui Yin; Hu Liu; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2024)

Sulfite activation of Fe-Mn bimetallic oxides for rapid oxidative removal of As(III) in water: Involvement of active Mn(III) - Guiyuan Cai; Yu Tian; Lipin Li; Wenxuan Zhang; Rui Huang; Jun Zhang; Qinyu Wang; Hua Xu; Yifeng Zhang (Chemical Engineering Journal, 2024)

Fermentation characteristics and prebiotic potential of enzymatically synthesized butyryl-fructooligosaccharides - Zixin Yang; Diming Tan; Weiwen Chen; Jun Hu; Rui Huang; Xiyang Wu; Milen I. Georgiev; Weibin Bai; Lingmin Tian (Carbohydrate Polymers, 2024)

Effect of vane angle on turbulence–chemistry interactions, temperature, flow field, burnout, and NOx emissions in swirling flames fueled by semicoke mixtures - Liutao Sun; Shengyu Kuang; Weilin Li; Jingjie Wang; Yanhui Xu; Lingkun Zhu; Hong Tian; Xinzhuo Li; Dengke Wang; Rui Sun (Environmental Science and Pollution Research, 2023)

O2 plasma-modified carbon nanotube for sulfamethoxazole degradation via peroxymonosulfate activation: Synergism of radical and non-radical pathways boosting water decontamination and detoxification - Shiqi Liu; Zichen Zhang; Rui Lu; Yuankun Mao; Huiru Ge; Can Liu; Chenxi Tian; Siyuan Yin; Li Feng; Yongze Liu; Chao Chen; Liqiu Zhang (Chemosphere, 2023)

RTAL: An edge computing method for real-time rice lodging assessment - Rui Gao; Penghao Chang; Dong Chang; Xin Tian; Yan Li; Zhiwen Ruan; Zhongbin Su (Computers and Electronics in Agriculture, 2023)

Utilization of halophytes in saline agriculture and restoration of contaminated salinized soils from genes to ecosystem: Suaeda salsa as an example - Chen Yang Li; Rui He; Chang Yan Tian; Jie Song (Marine Pollution Bulletin, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Synergistic effect triggered by Fe2O3 and oxygen-induced hydroxyl radical enhances formation of amino-phenolic humic-like substance - Yingchao Zhang; Zhitao Bi; Wenxin Tian; Zhenyu Ge; Yang Xu; Rui Xu; Hongqiong Zhang; Shoufeng Tang (Journal of Environmental Management, 2023)

Physicochemical stability of lichenan (Usnea longissima) decorated-selenium nanoparticles for cancer chemoprevention - Ziying Yang; Yajie Hu; Panpan Yue; Rui Tian; Huiling Li; Baozhong Lü; Gegu Chen; Feng Peng (Food Bioscience, 2023)

An interval water demand prediction method to reduce uncertainty: A case study of Sichuan Province, China - Xinyu Xia; Bin Liu; Rui Tian; Zuli He; Suyue Han; Ke Pan; Jingjing Yang; Yiting Zhang (Environmental Research, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

Potential of a winterschmidtiid prey mite for the production of the predatory mite Neoseiulus californicus (Acari: Phytoseiidae) - Rui Zhu; Jian-jun Guo; Tian-ci Yi; Fei Hou; Dao-chao Jin (Experimental and Applied Acarology, 2023)

Nanoplastic-Induced Biological Effects In Vivo and In Vitro: An Overview - Hongxin Xie; Xue Tian; Xiaoying Lin; Rui Chen; Saima Hameed; Liming Wang; Yong-Liang Yu; Bai Li; Yu-Feng Li (Reviews of Environmental Contamination and Toxicology, 2023)

Quantitative Estimation on Methane Storage Capacity of Organic-Rich Shales from the Lower Silurian Longmaxi Formation in the Eastern Sichuan Basin, China - Xiaowen Guo; Tao Luo; Tian Dong; Rui Yang; Yuanjia Han; Jizheng Yi; Sheng He; Zhiguo Shu; Hanyong Bao (Journal of Earth Science, 2023)

Biochar-derived dissolved organic matter (BDOM) and its influence on soil microbial community composition, function, and activity: A review - Muhammad Azeem; Tian-Ran Sun; Parimala Gnana Soundari Arockiam Jeyasundar; Rui-Xia Han; Hui Li; Hamada Abdelrahman; Sabry M. Shaheen; Yong-Guan Zhu; Gang Li (Critical Reviews in Environmental Science and Technology, 2023)

Insights of microalgal municipal wastewater treatment at low temperatures: Performance, microbiota patterns, and cold-adaptation of tubular and aeration column photobioreactors - Jiansong Tian; Pan Li; Yajun Luo; Heng Yan; Jian Liu; Zhicheng Pan; Yangwu Chen; Rui Wang; Yiwei Cheng; Houzhen Zhou; Junjie Li; Xin Li; et al. (Chemosphere, 2023)

A novel method of desynchronized operation of sails for ship wind-assisted propulsion system - Rui Zhang; Lianzhong Huang; Guisheng Peng; Ranqi Ma; Kai Wang; Feng Tian; Qiushi Song (Ocean Engineering, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Early clues and molecular mechanism involved in neurodegenerative diseases induced in immature mice by combined exposure to polypropylene microplastics and DEHP - Ge Yang; Cunyi Gong; Xinyue Zheng; Fei Hu; Jie Liu; Tian Wang; Xinyue Chen; Min Li; Zhihong Zhu; Ling Zhang; Rui Li (Environmental Pollution, 2023)

Comprehensive properties of non-penetrating and penetrating deep convection precipitation in summer over the Tibetan Plateau derived from GPM observations - Rui Wang; Zhongshan Jiang; Fengjiao Chen; Wenshou Tian; Liangliang Li; Hongying Tian; Jiali Luo (Atmospheric Research, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Quality assessment of the ionospheric density profiles based on long-term COSMIC 1 and 2 radio occultation observations - Na Fu; Rui Zhang; Qixin Pan; Xiaojing Tian; Shaoqiu Long; Chaolong Yao (Journal of Earth System Science, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Triterpenoid saponins from Psammosilene tunicoides and their antinociceptive activities - Yan-Hong Li; Xi-Shan Bai; Xiu-Xia Yang; Yu-Xiao Li; Hong-Rui Li; Zi-Liang Wang; Wei Wang; Kai Tian; Xiang-Zhong Huang (Phytochemistry, 2023)

Performance of a continuous micro-oxygen up-flow sludge bed reactor for assimilation of partial nitrification/anammox sludge into a CANON granular-floc system - Chenjie Wu; Liang Tian; Rui Huang; Yaguang Du; Dongyun Du (Journal of Environmental Chemical Engineering, 2023)

Characterization of a gE/gI/TK gene-deleted pseudorabies virus variant expressing the Cap protein of porcine circovirus type 2d - Rui-Qin Xu; Lin-Qing Wang; Hui-Hua Zheng; Run-Bo Tian; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

QSPR models for sublimation enthalpy of energetic compounds - Rui Liu; Yuechuan Tang; Jie Tian; Jing Huang; Chaoyang Zhang; Linyuan Wang; Jian Liu (Chemical Engineering Journal, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

A novel starch-based ethanol gel with contact-killing bacteria to cut off contact transmission of bacteria - Fu-Xiang Wei; Tian-Rui Zhou; Shao-Wei Zhong; Yong-Fu Deng; Chuan-Hui Xu; Li-Hua Fu; Bao-Feng Lin (Chemical Engineering Journal, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Integrative analyses of RNA-seq and ChIP-seq Reveal MITF as a Target Gene of TFPI-2 in MDA231 Cells - Guangli Wang; Gaofeng Zhang; Ningxia Zhu; Chunjiang Zhu; Mafei Kang; Guidan Zuo; Zhijie Niu; Wei Ye; Baodong Tian; Rui Cai (Biochemical Genetics, 2023)

Effects of atrazine on microbial metabolic limitations in black soils: Evidence from enzyme stoichiometry - Tiancong Gao; Haixia Tian; Ziqi Wang; Jing Shi; Rui Yang; Fang Wang; Leilei Xiang; Yunchao Dai; Mallavarapu Megharaj; Wenxiang He (Chemosphere, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Nitrate attenuation with rising groundwater levels: An integrated assessment using isotope tracers and microbial signatures - Jie Li; Yulian Liu; Wei Dai; Jian Li; Pingheng Yang; Lijun Tian; Shihang Yu; Rui Zuo; Yuanzheng Zhai; Wei Song; Fan Yang; Ruijing Zhou; et al. (Journal of Hydrology, 2023)

Achieving reasonable waste heat utilization in all truck operating conditions via a dual-pressure organic rankine cycle and its operating strategy - Xuanang Zhang; Xuan Wang; Jinwen Cai; Rui Wang; Xingyan Bian; Ping Yuan; Hua Tian; Gequn Shu (Journal of Cleaner Production, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Generation of gridded temperature map of constant-temperature layer based on meteorological data for shallow geothermal applications - Rui Mao; Zilong Zhao; Lei Tian; Tiantian Fang; Xinlei Wang (Geothermics, 2023)

Enzymatic synthesis of propionyl-fructooligosaccharides and their evaluation as a gut microbiota modulator - Diming Tan; Weiwen Chen; Zixin Yang; Minjing Rong; Rui Huang; Xiyang Wu; Weibin Bai; Lingmin Tian (Food Hydrocolloids, 2023)

Effects of superabsorbent polymers (SAPs) incorporated with organic and inorganic fertilizer on the water and nutrient retention of soil in rare earth mine tailing areas - Yanzi He; Zhiyuan Tian; Rui Ma; Yin Liang; Xuchao Zhu; Lili Qu (Journal of Soils and Sediments, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Experimental features of emissions and fuel consumption in a car-following platoon - Shirui Zhou; Junfang Tian; Ying-En Ge; Shaowei Yu; Rui Jiang (Transportation Research Part D: Transport and Environment, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Corrigendum to “Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char” [J. Hazard. Mater. 447 (2023) 130772] - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Inactivation of phage phiX174 by UV254 and free chlorine: Structure impairment and function loss - Miao Yu; Rui Gao; Xinyuan Lv; Minghao Sui; Tian Li (Journal of Environmental Management, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

International Nuclear Medicine Consensus on the Clinical Use of Amyloid Positron Emission Tomography in Alzheimer’s Disease - Mei Tian; Chuantao Zuo; Ali Cahid Civelek; Ignasi Carrio; Yasuyoshi Watanabe; Keon Wook Kang; Koji Murakami; Valentina Garibotto; John O. Prior; Henryk Barthel; Yihui Guan; Jiaying Lu; et al. (Phenomics, 2023)
Alzheimer’s disease (AD) is the main cause of dementia, with its diagnosis and management remaining challenging. Amyloid positron emission tomography (PET) has become increasingly important in medical practice for patients with AD. To integrate and update previous guidelines in the field, a task group of experts of several disciplines from multiple countries was assembled, and they revised and approved the content related to the application of amyloid PET in the medical settings of cognitively impaired individuals, focusing on clinical scenarios, patient preparation, administered activities, as well as image acquisition, processing, interpretation and reporting. In addition, expert opinions, practices, and protocols of prominent research institutions performing research on amyloid PET of dementia are integrated. With the increasing availability of amyloid PET imaging, a complete and standard pipeline for the entire examination process is essential for clinical practice. This international consensus and practice guideline will help to promote proper clinical use of amyloid PET imaging in patients with AD.

Selective CDK9 knockdown sensitizes TRAIL response by suppression of antiapoptotic factors and NF-kappaB pathway - Qian Yuan; Kui Su; Shuyi Li; Xinyi Long; Lang Liu; Jianwu Sun; Xin Yuan; Minghui Yang; Rui Tian; Wanting Zhang; Zhujie Deng; Quanjiang Li; et al. (Apoptosis, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Soil variables and reflected light revealed the plasticity of grape and wine composition: Regulation of the flavoromics under inner row gravel covering - Meng-Bo Tian; Wan-Hui Ma; Nong-Yu Xia; Jing Peng; Rui-Qi Hu; Chang-Qing Duan; Fei He (Food Chemistry, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Strontium isotope ratios in kidney stones reveal the environmental implications for humans in Beijing, China - Rui Qu; Guilin Han; Yu Tian; Ye Zhao (Environmental Geochemistry and Health, 2023)

Circular RNA circAKIRIN2 participates in the process of stress-induced immunosuppression affecting immune response to infectious bursal disease virus vaccine in chicken - Yufei Tian; Xiaoli Ma; Yi Jiang; Jianwei Han; Rui Zhang; Xinxin Xu; Wei Zhang; Chaolai Man (Veterinary Microbiology, 2023)

Developing practical and small-scale radio frequency technology for tempering minced chicken breast at home - Yingqi Tian; Mengge Li; Xiangyu Guan; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Screening of goaty flavor-inhibiting lactic acid bacteria and their effects on the flavor profiles of goat milk cakes - Huaixiang Tian; Rui Yang; Xuefeng Sun; Haiyan Yu; Juan Huang; Haibin Yuan; Xinman Lou; Zhaohu Yuan; Chen Chen (Food Bioscience, 2023)

Internet addiction-induced brain structure and function alterations: a systematic review and meta-analysis of voxel-based morphometry and resting-state functional connectivity studies - Jing-Ting Sun; Bo Hu; Tian-Qi Chen; Zhu-Hong Chen; Yu-Xuan Shang; Yu-Ting Li; Rui Wang; Wen Wang (Brain Imaging and Behavior, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Canola oil substitution doesn't affect growth but alters fillet quality of triploid rainbow trout - Lingling Guan; Linying Zhuo; Haining Tian; Changzhong Li; Jianrong Li; Yuqiong Meng; Rui Ma (Aquaculture, 2023)

Application of wavelet-packet transform driven deep learning method in PM2.5 concentration prediction: A case study of Qingdao, China - Qinghe Zheng; Xinyu Tian; Zhiguo Yu; Nan Jiang; Abdussalam Elhanashi; Sergio Saponara; Rui Yu (Sustainable Cities and Society, 2023)

The hybridization origin of the Chinese endemic herb genus Notopterygium (Apiaceae): Evidence from population genomics and ecological niche analysis - Yun Jia; Mi-Li Liu; Jordi López-Pujol; Rui-Wen Jia; Yi-Xuan Kou; Ming Yue; Tian-Xia Guan; Zhong-Hu Li (Molecular Phylogenetics and Evolution, 2023)

Depositional-diagenetic process and their implications for pore development of Wufeng-Longmaxi shales in the Jiangdong block, Fuling shale gas field, SW China - Kefei Chen; Rui Yang; Hanyong Bao; Tian Dong; Aoqi Jia; Qinhong Hu; Xiaowen Guo; Sheng He (Marine and Petroleum Geology, 2023)

High-resolution records of sea surface temperature and salinity in the East China Sea over the past 14.2 kyr: Implication from alkenone and its hydrogen isotopes - Rui Zhang; Wenlong Pei; Yipeng Wang; Xinling Wang; Jiayue Wang; Tiegang Li; James Russell; Fan Zhang; Zhiyong Liu; Minglei Guan; Qi Han; Chenyang Tian; et al. (Global and Planetary Change, 2023)

Structural incorporation of iron influences biomethylation potential of mercury sulfide - Yunyun Ji; Shan Gao; Rui Si; Zhanhua Zhang; Li Tian; Wenyu Guan; Weichao Wang; Jiubin Chen; Wei Chen; Pedro J.J. Alvarez; Tong Zhang (Geochimica et Cosmochimica Acta, 2023)

Mechanisms of lithium selection from mixed LiCl-NaCl solution by nanopores: The synergistic effects of nanoconfinement and electric fields - Gang Liao; Xing-Yi Yue; Shi-Qi Zheng; Rui-Tian Ma; Hai-Bo Yi (Desalination, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Future land-use change and its impact on terrestrial ecosystem carbon pool evolution along the Silk Road under SDG scenarios - Min Cao; Ya Tian; Kai Wu; Min Chen; Yu Chen; Xue Hu; Zhongchang Sun; Lijun Zuo; Jian Lin; Lei Luo; Rui Zhu; Zhenci Xu; et al. (Science Bulletin, 2023)

Estimating the maximum vegetation coverage and productivity capacity supported by rainwater resources on the Loess Plateau - Yao Li; Baoqing Zhang; Rui Shao; Tongxuan Su; Xuejin Wang; Lei Tian; Chansheng He (Journal of Hydrology, 2023)

Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

An ultra-thin chemical vapor deposited polymer interlayer to achieve highly improved stability of perovskite solar cell - Jing Zhou; Xueying Tian; Rui Chen; Weitao Chen; Xin Meng; Xinyu Guan; Jianan Wang; Sanwan Liu; Fumeng Ren; Shasha Zhang; Yiqiang Zhang; Zonghao Liu; et al. (Chemical Engineering Journal, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Co-cultivation of microalgae-activated sludge for municipal wastewater treatment: Exploring the performance, microbial co-occurrence patterns, microbiota dynamics and function during the startup stage - Xin Li; Jian Liu; Jiansong Tian; Zhicheng Pan; Yangwu Chen; Fei Ming; Rui Wang; Lin Wang; Houzhen Zhou; Junjie Li; Zhouliang Tan (Bioresource Technology, 2023)

Understanding the Origin and Evolution of Tea (Camellia sinensis [L.]): Genomic Advances in Tea - Zai-Bao Zhang; Tao Xiong; Jia-Hui Chen; Fan Ye; Jia-Jia Cao; Yu-Rui Chen; Zi-Wei Zhao; Tian Luo (Journal of Molecular Evolution, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Determination and prediction of digestible energy, metabolizable energy, and standardized ileal digestibility of amino acids in barley for growing pig - Rui Li; Mingzhou Tian; Ganyi Feng; Gaifeng Hou; Xianji Jiang; Gang Yang; Qiang Xiang; Xiaojie Liu; Cimi Long; Ruilin Huang; Yulong Yin (Animal Feed Science and Technology, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Exploring the heterogeneity in drivers of energy-saving behaviours among hotel guests: Insights from the theory of planned behaviour and personality profiles - Qian-Cheng Wang; Yi-Tian Ren; Xuan Liu; Rui-Dong Chang; Jian Zuo (Environmental Impact Assessment Review, 2023)

Tissue-resident immune cells in the pathogenesis of multiple sclerosis - Jie Tian; Lingli Jiang; Zixiang Chen; Qingfang Yuan; Chang Liu; Longfeng He; Feng Jiang; Ke Rui (Inflammation Research, 2023)

Early life history affects fish size mainly by indirectly regulating the growth during each stage: a case study in a demersal fish - Rui Wu; Qinghuan Zhu; Satoshi Katayama; Yongjun Tian; Jianchao Li; Kunihiro Fujiwara; Yoji Narimatsu (Marine Life Science & Technology, 2023)

Effects of varying levels of crawfish (Procambarus clarkia) shell meals on growth, fillet quality, and health of koi carp (Cyprinus carpio) - Xiaofei Cheng; Jin Xiang; Jingjing Tian; Xing Tian; Hao Wu; Xiping Yuan; Zhigang He; Min Xie; Rui Song (Aquaculture, 2023)

Ultrasensitive hydrogel grating detector for real-time continuous-flow detection of trace threat Pb2+ - Xiao-Yu Tian; Meng-Wei Sun; Guo-Yu Wen; Min Cao; Da-Wei Pan; Rui Xie; Xiao-Jie Ju; Zhuang Liu; Wei Wang; Liang-Yin Chu (Journal of Hazardous Materials, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Metagenomic insights into bacterial communities and functional genes associated with texture characteristics of Kazakh artisanal fermented milk Ayran in Xinjiang, China - Malina Kuerman; Rui Wang; Yu Zhou; Xiaoying Tian; Qingyu Cui; Huaxi Yi; Pimin Gong; Zhe Zhang; Kai Lin; Tongjie Liu; Lanwei Zhang (Food Research International, 2023)

Low-cost mineral packing materials improve DOM and micropollutants removal from landfill leachate in ozonation bubble columns: Insights into the enhancement mechanisms and applicability of surrogate-based monitoring - Xuetong Yang; Changtao Chen; Tao Zhang; Xiang Tian; Rui Zhang; Dave Manhaeghe; Yunliang Zhao; Shaoxian Song; Kristof Demeestere; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Z- scheme heterojunction of BiOI nanosheets grown in situ on NH2-UiO-66 crystals with rapid degradation of BPA in real water - Rui Ji; Zhuzhu Zhang; Lechen Tian; Liujun Jin; Qingfeng Xu; Jianmei Lu (Chemical Engineering Journal, 2023)

Rapid and massive fractionation of hemicelluloses for purifying cellulose at room temperature by tetramethylammonium hydroxide - Rui Tian; Bolang Zhu; Qiaoling Liu; Yajie Hu; Ziying Yang; Jun Rao; Yuying Wu; Baozhong Lü; Jing Bian; Feng Peng (Bioresource Technology, 2023)

A Medicago truncatula lncRNA MtCIR1 negatively regulates response to salt stress - Rui Tian; Xiaohan Sun; Cuimei Liu; Jinfang Chu; Mingui Zhao; Wen-Hao Zhang (Planta, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

HIF-1α promotes paraquat induced acute lung injury and implicates a role NF-κB and Rac2 activity - Yong Zhu; Xiaoxiao Meng; Wenyu Yang; Jinfeng Wang; Jiaxiang Zhang; Rui Tian; Ruilan Wang; Qi Su; Wei Jin (Toxicology, 2023)

The formation of supercritical carbon dioxide hydrothermal vents in the Okinawa Trough - Fanfan Tian; Rui Li; Guozhi Xie; Kun Wang; Lipeng Zhang; Xin Zhang; Weidong Sun (Science Bulletin, 2023)

Evaluating performances of a small-scale 50 Ω radio frequency heating system designed for home applications - Yingqi Tian; Xiangyu Guan; Rui Li; Hosahalli Ramaswamy; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2023)

Experimental and theoretical study on the transformation of typical organic sulfur during hydrothermal carbonization of sludge - Shan Cheng; Jingchun Huang; Rui Luo; Hong Tian; Yanshan Yin; Yu Qiao (Fuel, 2023)

Janus fibrous membrane with directional liquid transport capacity for wound healing promotion - Haohong Pi; Yanli Xi; Jing Wu; Miaomiao Hu; Boyang Tian; Yiwen Yang; Rui Wang; Xiuqin Zhang (Chemical Engineering Journal, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Rationally tailoring anion traps into electrospun nanofibers for highly efficient perrhenate/pertechnetate capture - Dingyang Chen; Zhaoli Liu; Shuying Li; Xiaofei Jing; Yuyang Tian; Wei Hu; Fengchao Cui; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2023)

Yeast cell wall polysaccharides in Tibetan kefir grains are key substances promoting the formation of bacterial biofilm - XiaoMeng Wang; XueLiang Zhang; YuKe Wang; NanYu Tang; LuYao Xiao; JuanJuan Tian; Xin Rui; Wei Li (Carbohydrate Polymers, 2023)

Rapid, selective, and room temperature dissolution of crystalline xylan by a hydrotrope - Qiaoling Liu; Rui Tian; Ziwen Lv; Yuying Wu; Baozhong Lv; Xiang Hao; Zhimin Xue; Feng Peng (Carbohydrate Polymers, 2023)

Precise orbit determination for BDS-3 GEO satellites enhanced by intersatellite links - Xiaojie Li; Xiaogong Hu; Rui Guo; Chengpan Tang; Shuai Liu; Jie Xin; Jinglei Guo; Yijun Tian; Yufei Yang; Jianhua Yang; Xinglong Zhao (GPS Solutions, 2023)

Insight into mechanisms of heavy metal-induced natural clay aggregation - Qinyi Li; Rui Tian; Qingyuan Yang (Applied Clay Science, 2023)

Graphene electrochemical transistor incorporated with gel electrolyte for wearable and non-invasive glucose monitoring - Nan Gao; Rui Zhou; Bo Tu; Tian Tao; Yongqiao Song; Zhiwei Cai; Hanping He; Gang Chang; Yuxiang Wu; Yunbin He (Analytica Chimica Acta, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Oxidative stress and inflammation caused by 1-tetradecyl-3-methylimidazolium tetrafluoroborate in rat livers - Huafei Yuan; Feng Xu; Xingxing Tian; Haiyan Wei; Rui Zhang; Yueyue Ge; Hongmei Xu (Environmental Science and Pollution Research, 2022)

Enhancing extracellular electron transfer through selective enrichment of Geobacter with Fe@CN-modified carbon-based anode in microbial fuel cells - Xiao-Long Cheng; Qiang Xu; Qian-Wen Yang; Rui-Rui Tian; Biao Li; Su Yan; Xue-Ying Zhang; Jun Zhou; Xiao-Yu Yong (Environmental Science and Pollution Research, 2022)

Risk Assessment and Source Identification of Arsenic in Surface Sediments from Caohai Lake, China - Ying Tang; Xinmin Liu; Rui Tian; Rui Li; Hang Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Long non-coding RNA RPL34-AS1 ameliorates oxygen–glucose deprivation-induced neuronal injury via modulating miR-223–3p/IGF1R axis - Xin-ya Wei; Tian-qi Zhang; Rui Suo; You-yang Qu; Yan Chen; Yu-lan Zhu (Human Cell, 2022)

Impact of climate change on long-term variations of small yellow croaker (Larimichthys polyactis) winter fishing grounds - Rui Zhang; Yang Liu; Hao Tian; Shuhao Liu; Kaiwei Zu; Xinmei Xia (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ) is one of the key demersal species with high economic values and wide distribution in the China Seas. In this study, a Winter Fishing ground Abundance Index (WFAI) was developed by using fisheries survey data in 1971–1982 and used as the response variable to investigate the impacts of environmental variables, including surface current velocity (SCV), sea surface salinity (SSS), sea surface temperature (SST), and depth (DE). A total of 45 combinatorial generalized additive models (GAMs), generalized linear models (GLMs), and random forest models (RFs) were used to select the optimal WFAI prediction. The final WFAI distribution results showed that the winter fishing ground hotspots of small yellow croaker were mainly distributed between 11°C and 16°C isotherms and between 50-m and 100-m isobaths, and the area of winter fishing ground hotspots (WFHA) significantly decreased and the hotspots tended to move northward over the past 50 years. The shape of hotspots was strongly affected by temperature fronts and salinity fronts. Analysis with the climate indices revealed that the Atlantic Multidecadal Oscillation (AMO) might have a large influence on the distribution of small yellow croaker by affecting SST and SSS in the China Seas more than the Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO), and Arctic Oscillation Index (AOI). The future prediction based on two extreme scenarios (RCP2.6 and RCP8.5) indicated that the hotspots would obviously move northward. These findings will serve effectively the fishery resources monitoring, management, and evaluation of small yellow croaker in the China Seas.

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

Plant-mediated rhizospheric interactions in rice and water spinach intercropping enhance Si uptake by rice - Chuanchuan Ning; Lei Wang; Rui Liu; Taowen Pan; Yixia Cai; Jihui Tian; Shiming Luo; Kunzheng Cai (Plant and Soil, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Detection and typing of dengue virus by one-step RT-PCR-based high-resolution melting assay - Rui Tian; Hao Yan; Yang Jiang; Aiping Wu; Ling Li; Zhangnv Yang; Kuangming Yu (Virus Genes, 2022)

Temporal Dynamics in Energy Fluxes and Trophic Structure of a Portunus trituberculatus Polyculture Ecosystem During Different Culture Periods - Jie Feng; Xiang-Li Tian; Shuang-Lin Dong; Rui-Peng He; Kai Zhang; Dong-Xu Zhang; Qing-Qi Zhang (Frontiers in Marine Science, 2022)
Swimming crab ( Portunus trituberculatus ) are an important aquaculture species in eastern coastal areas of China. To improve the understanding of P. trituberculatus culture ecosystem functioning, the dynamics of energy flow and trophic structure of a P. trituberculatus polyculture system (co-culture with white shrimp Litopenaeus vannamei and short-necked clam Ruditapes philippinarum ) were investigated in this study. Three Ecopath models representing the early, middle, and late culture periods of a P. trituberculatus polyculture ecosystem, respectively, were constructed to compare ecosystem traits at different culture periods. The results demonstrated that detritus was the main energy source in this polyculture ecosystem, and most of the total system throughput occurred at trophic levels I and II. Artificial food input and consumption by the culture organisms increased from early to middle and late periods, which produced marked impacts on biomass structure and primary production. R. philippinarum was considered to have a dominant influence on phytoplankton community dynamics which changed from nano- to pico-phytoplankton predominance, from the middle to the late period. Considering the low utilization efficiency of pico-phytoplankton production, large amounts of detritus accumulated in the sediment in the late period, which may constitute a potential risk for the ecosystem. Ecological network analyses indicated that the total energy flow and level of system organization increased from the early to the middle and late periods, whereas food web complexity and system resilience decreased from early to middle and late periods, which may indicate a trend of decreasing ecosystem stability. The system may be further optimized by increased stocking density of R. philippinarum and by introducing macro-algae at a suitable biomass to increase ecosystem stability, energy utilization efficiency, and aquaculture production.

Sandstorms cause shrinkage of Haloxylon ammodendron shrubs and limit their self-renewal - Sheng-bo Shi; Dang-wei Zhou; Fang-lin Wang; Rui Shi; Tao Sun; Tian-cai Li; Jia-lin Ma; Xiang Wan; Jian-ping Ma; Jing-nian Tang (Theoretical and Experimental Plant Physiology, 2022)
Haloxylon ammodendron is an excellent windproof and sand-fixing species whose shrubs are widely cultivated in arid desert areas of northwest China but are now at risk of degradation and shrinkage. Using the chlorophyll fluorescence image analysis technique, the response of photosystem II (PSII) photochemical efficiency and non-photochemical quenching capacity to sediment-carrying wind and sand-free wind (both 12 m s −1 ) lasting for 10, 20, and 40 min were studied with seedlings in a wind tunnel. The results indicated that the sand-free wind had little influence on the maximum quantum efficiency of PSII photochemistry, F v / F m , which was approximately 0.80 on average; however, the F v / F m decreased over exposure time in the sediment-carrying wind group, with values smaller than those in the wind-only group. The non-photochemical quenching was sensitive to wind erosion, and sediment-carrying wind could aggravate the reduction in non-photochemical quenching ( NPQ ). Except for the 10 min duration, the maximum quantum efficiency of PSII photochemistry after dark recovery for 15 min, F v r / F m r , was lower in seedlings exposed to sediment-carrying wind than in those in the wind-only group. Compared to wind-only, wind-blown sand led to a water imbalance and withering in seedlings, causing the concentration of photosynthetic pigments (when based on the fresh mass of green branches) to not decrease. With a longer exposure time to sediment-carrying wind, both the probability and extent of lignified spots occurring increased in green assimilative branches. Our results demonstrated that sediment-carrying wind at 12 m s −1 lasting for 20 min or more could cause irreversible damage to the photosynthetic apparatus of H. ammodendron seedlings. Therefore, frequent and strong sandstorms are the main disturbance factors leading to shrinkage of shrubs and limiting their self-renewal.

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Characterization of chikusetsusaponin IV and V induced apoptosis in HepG2 cancer cells - Tian Zuo; Zuo Zhang; Peng Jiang; Rui Zhang; Danni Ni; Yuan Yuan; Shaopeng Zhang (Molecular Biology Reports, 2022)

The interplay of particle properties and solution chemistry on aggregation kinetics of soil nanoparticles - Ning Hu; Chen-yang Xu; Zeng-chao Geng; Fei-nan Hu; Qi-rui Li; Ren-tian Ma; Qiang Wang (Journal of Soils and Sediments, 2022)

In vitro Scolicidal Efficacy of 5-Fluorouracil and Radiation Against Protoscoleces of Echinococcus granulosus Sensu Lato - Pengfei Lu; Jun Li; Rui Mao; Hongzhi Qi; Liping Yang; Qin Zhou; Mengxiao Tian; Wenbao Zhang; Yongxing Bao (Acta Parasitologica, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Application of nanostructures as antimicrobials in the control of foodborne pathogen - Yu Tian; Rui Cai; Tianli Yue; Zhenpeng Gao; Yahong Yuan; Zhouli Wang (Critical Reviews in Food Science and Nutrition, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Positron Emission Tomography Molecular Imaging for Phenotyping and Management of Lymphoma - Xiaohui Zhang; Han Jiang; Shuang Wu; Jing Wang; Rui Zhou; Xuexin He; Shufang Qian; Shuilin Zhao; Hong Zhang; Ali Cahid Civelek; Mei Tian (Phenomics, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Secondary metabolites isolated from Agrimonia pilosa Ledeb. - Hong-Rui Li; Yu-Kui Li; Jian Xiao; Cui Yang; Meng-Yuan Jiang; Kai Tian; Wei Wang; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2022)

Qaidamihabitans albus gen. nov., sp. nov., a new member of the family Pseudonocardiaceae, and transfer of Prauserella shujinwangii to Qaidamihabitans gen. nov. as Qaidamihabitans shujinwangii comb. nov. - Li-Sha Tian; Gang-Qiang Jiang; Rui Li; Ping Ni; Chuan-En Li; Hong-Yan Zhang; Juan Wang; Xiao-Ping Zhang; Yun Wang; Shu-Kun Tang (Archives of Microbiology, 2021)

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

Dietary selenium requirement of coho salmon (Oncorhynchus kisutch W.) alevins - Lian-cai Du; Hai-rui Yu; Ling-yao Li; Qin Zhang; Qi Tian; Jin-qian Liu; Ling-ling Shan (Aquaculture International, 2021)

Genetic control of Fusarium head blight resistance in two Yangmai 158-derived recombinant inbred line populations - Haisheng Yan; Guoqiang Li; Jinxing Shi; ShunShun Tian; Xiaoqiu Zhang; Rui Cheng; Xin Wang; Yang Yuan; Shouyang Cao; Jiyang Zhou; Zhongxin Kong; Haiyan Jia; et al. (Theoretical and Applied Genetics, 2021)

Oxiracetam Mediates Neuroprotection Through the Regulation of Microglia Under Hypoxia-Ischemia Neonatal Brain Injury in Mice - Dan Wang; Yanbang Wei; Jingxia Tian; Dong He; Rui Zhang; Xiaoshuai Ji; Xiaoming Huang; Jun Sun; Jiajia Gao; Zixiao Wang; Qi Pang; Qian Liu (Molecular Neurobiology, 2021)

Gradually evaluating of suicidal risk in depression by semi-supervised cluster analysis on resting-state fMRI - Zhongpeng Dai; Xiangyu Shen; Shui Tian; Rui Yan; Huan Wang; Xinyi Wang; ZhiJian Yao; Qing Lu (Brain Imaging and Behavior, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Longitudinal associations of sleep duration and sleep quality with coronary heart disease risk among adult population: classical meta-analysis and Bayesian network meta-analysis - Rui Zeng; Yu-ting Jiang; Tian-wu Chen; Dan-dan Guo; Rui Li (Sleep and Biological Rhythms, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Changes in water use efficiency and their relations to climate change and human activities in three forestry regions of China - Jiaxi Tian; Zengxin Zhang; Rui Kong; Bin Zhu; Fengying Zhang; Shanshan Jiang; Xi Chen (Theoretical and Applied Climatology, 2021)

Optimizing Protein-Glutaminase Expression in Bacillus subtilis - Xiaoying Ouyang; Yingjie Liu; Ruidan Qu; Min Tian; Ting Yang; Rui Zhu; Hongliang Gao; Mingfei Jin; Jing Huang (Current Microbiology, 2021)

Diarylpropanes from Horsfieldia kingii - Bo Liu; Ye-Gao Chen; Xing-Jun Tian; Rui Zhan (Natural Product Research, 2021)

Leaf Transcriptome and Weight Gene Co-expression Network Analysis Uncovers Genes Associated with Photosynthetic Efficiency in Camellia oleifera - Zhilong He; Caixia Liu; Xiangnan Wang; Rui Wang; Yun Tian; Yongzhong Chen (Biochemical Genetics, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

Culturing novel and abundant pelagiphages in the ocean - Zefeng Zhang; Fang Qin; Feng Chen; Xiao Chu; Haiwei Luo; Rui Zhang; Sen Du; Zhen Tian; Yanlin Zhao (Environmental Microbiology, 2021)
Summary Viruses play a key role in biogeochemical cycling and host mortality, metabolism, physiology and evolution in the ocean. Viruses that infect the globally abundant SAR11 bacteria (pelagiphages) were reported to be an important component of the marine viral communities. Our current knowledge of pelagiphages is based on a few studies and therefore is limited. In this study, 10 new pelagiphages were isolated and genomically characterized. These pelagiphages represent the first cultivated representatives of four viral lineages only found in metagenomic sequencing datasets previously. Many abundant environmental viral sequences, i.e., single‐virus vSAG 37‐F6 and several Global Ocean Viromes (GOV) viral populations, are now further confirmed with these pelagiphages. Viromic read mapping reveals that these new pelagiphages are globally distributed in the ocean and can be detected throughout the water column. Remarkably, isolation of these pelagiphages contributed up to 12% of all viromic reads annotated in the analysed viromes. Altogether, this study has greatly broadened our understanding of pelagiphages regarding their morphology, genetic diversity, infection strategies, and distribution pattern. The availability of these newly isolated pelagiphages and their genome sequences will allow us to further explore their infectivities and ecological strategies.

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

Fabrication of Nanosuspensions to Improve the Oral Bioavailability of Total Flavones from Hippophae rhamnoides L. and their Comparison with an Inclusion Complex - Rui Tian; Hui Wang; Yi Xiao; Pengyue Hu; Ruofei Du; Xiufeng Shi; Zhengtao Wang; Yan Xie (AAPS PharmSciTech, 2020)

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

Remediation of Trichloroethylene-Contaminated Groundwater by Sulfide-Modified Nanoscale Zero-Valent Iron Supported on Biochar: Investigation of Critical Factors - Jie Chen; Haoran Dong; Ran Tian; Rui Li; Qianqian Xie (Water, Air, & Soil Pollution, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Reduction of heavy metals leaching and pore volume in high-volume fly ash cement pastes by adding nano-SiO2 - Qian Huang; Shuai Tang; Ya You; Yibo Chen; Haisen Deng; Rui Tian (Environmental Science and Pollution Research, 2020)

Sulfur content in coal formed during different geologic periods in the Guangxi Province and the relationship with the depositional environment - Bohui Xu; Yuxin Song; Yuan Tian; Rui Yang; Fei Xu; Shuli Ding; Pengfei Sun (Arabian Journal of Geosciences, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Phosphorus transportation in runoff as influenced by cationic non-classic polarization: a simulation study - Ying Chen; Rui Tian; Hang Li (Journal of Soils and Sediments, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Digestive characteristics and blood chemistry profile of triploid rainbow trout Oncorhynchus mykiss: influence of body size and seasonal variation - Yuqiong Meng; Buying Han; Changzhong Li; Kangkang Qian; Xiaohong Liu; Xuemin Hu; Xu Yang; Haining Tian; Rui Ma (Fisheries Science, 2019)

The effect of interactions between particles on soil infiltrability - Wuquan Ding; Xinmin Liu; Feinan Hu; Hualing Zhu; Yaxue Luo; Song Li; Rui Tian; Bing Bao; Hang Li (Journal of Soils and Sediments, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Depositional facies and stratal cyclicity of carbonate successions in the Yingshan and Yijianfang Group (Lower-Middle Ordovician) in Yuejin-Tuoputai Region, Tarim Basin, NW China - Cunli Jiao; Zhao Xue-Qin; Rui Zhao; Li Hui-Li; Liu Tian-Jia; Zhao Jia-Hui (Carbonates and Evaporites, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Urinary bisphenol A (BPA) concentrations and exposure predictors among pregnant women in the Laizhou Wan Birth Cohort (LWBC), China - Shasha Zhao; Caifeng Wang; Rui Pan; Rong Shi; Weiye Wang; Ying Tian (Environmental Science and Pollution Research, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Solute Geochemistry and Multivariate Analysis of Water Quality in the Guohua Phosphorite Mine, Guizhou Province, China - Peiyue Li; Rui Tian; Rong Liu (Exposure and Health, 2019)

Antioxidant defense against rust infection in the leaf tissue of Malus crabapple - Yudan Duan; Suxiao Hao; Rui Luo; Yanfen Lu; Ge Li; Jie Zhang; Ji Tian; Yuncong Yao (Acta Physiologiae Plantarum, 2019)

Theory to describe incomplete ion exchange in charged heterogeneous systems - Wei Du; Xinmin Liu; Rui Li; Rui Tian; Wuquan Ding; Hang Li (Journal of Soils and Sediments, 2019)

An efficient karst fracture seepage path construction algorithm based on a generalized disk model - Xiaoping Rui; Tian Yu (Arabian Journal of Geosciences, 2019)

Enhanced water solubility, antioxidant activity, and oral absorption of hesperetin by D-α-tocopheryl polyethylene glycol 1000 succinate and phosphatidylcholine - Su-Fang Gu; Li-Ying Wang; Ying-Jie Tian; Zhu-Xian Zhou; Jian-Bin Tang; Xiang-Rui Liu; Hai-Ping Jiang; You-Qing Shen (Journal of Zhejiang University-SCIENCE B, 2019)

Long noncoding RNA UCA1 promotes the proliferation of hypoxic human pulmonary artery smooth muscle cells - Tian-Tian Zhu; Rui-Li Sun; Ya-Ling Yin; Jin-Ping Quan; Ping Song; Jian Xu; Ming-Xiang Zhang; Peng Li (Pflügers Archiv - European Journal of Physiology, 2019)

Two new lignans from Horsfieldia kingii - Bo Liu; Shou-Zhen Du; Fang Kuang; Ying Liu; Xing-Jun Tian; Ye-Gao Chen; Rui Zhan (Natural Product Research, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Seasonal Hydrochemical Characterization and Groundwater Quality Delineation Based on Matter Element Extension Analysis in a Paper Wastewater Irrigation Area, Northwest China - Peiyue Li; Song He; Xiaodong He; Rui Tian (Exposure and Health, 2018)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Alzheimer’s Disease Risk Variant rs2373115 Regulates GAB2 and NARS2 Expression in Human Brain Tissues - Guiyou Liu; Tao Wang; Rui Tian; Yang Hu; Zhifa Han; Pingping Wang; Wenyang Zhou; Peng Ren; Jian Zong; Shuilin Jin; Qinghua Jiang (Journal of Molecular Neuroscience, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Ancylomarina psychrotolerans sp. nov., isolated from sediments of Fildes Peninsula and emended the description of genus Ancylomarina - Chao Jia; Hong-chang Cui; Yan-qiong Han; Tian-yu Fu; Rui Du; Xiao-lei Wang; Xiao-chong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2018)

Composition and antimicrobial activity of the essential oil from the branches of Jacaranda cuspidifolia Mart. growing in Sichuan, China - Juanjuan Yuan; Tian Gan; Yingtian Liu; Hui Gao; Weifeng Xu; Tao Zhang; Rui Tan; Zhenghong Cai; Hezhong Jiang (Natural Product Research, 2018)

An adaptive sampling approach to reduce uncertainty in slope stability analysis - Jing-Sen Cai; Tian-Chyi Jim Yeh; E-Chuan Yan; Rui-Xuan Tang; Jet-Chau Wen; Shao-Yang Huang (Landslides, 2018)

Identification and verification of pleiotropic QTL controlling multiple amino acid contents in soybean seed - Xihuan Li; Rui Tian; Samson Kamala; Hui Du; Wenlong Li; Youbin Kong; Caiying Zhang (Euphytica, 2018)

Geochemistry, Hydraulic Connectivity and Quality Appraisal of Multilayered Groundwater in the Hongdunzi Coal Mine, Northwest China - Peiyue Li; Jianhua Wu; Rui Tian; Song He; Xiaodong He; Chenyang Xue; Kang Zhang (Mine Water and the Environment, 2018)

Nutrient Decomposition Rate and Sugarcane Yield as Influenced by Mung Bean Intercropping and Crop Residue Recycling - Tie-Guang He; Li-Rong Su; Yang-Rui Li; Tian-Ming Su; Fang Qin; Qin Li (Sugar Tech, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Ursolic acid, a potential anticancer compound for breast cancer therapy - Ran Yin; Tong Li; Jing Xin Tian; Pan Xi; Rui Hai Liu (Critical Reviews in Food Science and Nutrition, 2018)

Response of soil physical and chemical properties to Rocky desertification succession in South China Karst - Maoyin Sheng; Kangning Xiong; Linjiao Wang; Xiaona Li; Rui Li; Xingjun Tian (Carbonates and Evaporites, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Metatranscriptomics analysis of cyanobacterial aggregates during cyanobacterial bloom period in Lake Taihu, China - Zhenzhu Chen; Junyi Zhang; Rui Li; Fei Tian; Yanting Shen; Xueying Xie; Qinyu Ge; Zuhong Lu (Environmental Science and Pollution Research, 2018)

Three new polyketides from the marine sponge-derived fungus Trichoderma sp. SCSIO41004 - Xiaoyan Pang; Xiuping Lin; Yongqi Tian; Rui Liang; Junfeng Wang; Bin Yang; Xuefeng Zhou; Kumaravel Kaliyaperumal; Xiaowei Luo; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Pollution characteristics and ecological risk assessment of HCHs and DDTs in estuary wetland sediments from the Bohai Bay, North China - Qing Liu; Shengyan Tian; Rui Jia; Xianbin Liu (Environmental Science and Pollution Research, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Comparative study of the leaf transcriptomes and ionoms of Juglans regia and its wild relative species Juglans cathayensis - Zhongcheng Zhou; Muxian Han; Mei Hou; Xiaojing Deng; Rui Tian; Shuifa Min; Jinbo Zhang (Acta Physiologiae Plantarum, 2017)

Spatiotemporal Variability of Contaminants in Lake Water and Their Risks to Human Health: A Case Study of the Shahu Lake Tourist Area, Northwest China - Peiyue Li; Wei Feng; Chenyang Xue; Rui Tian; Siting Wang (Exposure and Health, 2017)

Molecular Mechanisms of Vascular Dementia: What Can Be Learned from Animal Models of Chronic Cerebral Hypoperfusion? - Si-Qi Du; Xue-Rui Wang; Ling-Yong Xiao; Jian-Feng Tu; Wen Zhu; Tian He; Cun-Zhi Liu (Molecular Neurobiology, 2017)

Remains of trilobites and other species discovered in a volcanic ash bed of the end-Permian, Yangtze craton, South China - Zejin Shi; Leixun Lu; Guan Yin; Hongyu Long; Wenjie Li; Huaixin Yang; Rui Cao; Xuesong Tian; Qian Tan; Kun Wang; Yong Wang; Yaming Tian (International Geology Review, 2017)

Seco-pregnane glycosides from the stems of Epigynum auritum - Fei Gao; Yuan-Cheng Yao; Zong Wan; Sheng-Bao Cai; Jian Fan; Tian-Rui Zhao; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Progress, opportunities, and key fields for groundwater quality research under the impacts of human activities in China with a special focus on western China - Peiyue Li; Rui Tian; Chenyang Xue; Jianhua Wu (Environmental Science and Pollution Research, 2017)

Characterization of uncultivated magnetotactic bacteria from the sediments of Yuehu Lake, China - Haijian Du; Rui Zhang; Wenyan Zhang; Cong Xu; Yiran Chen; Hongmiao Pan; Ke Zhou; Long-fei Wu; Tian Xiao (Acta Oceanologica Sinica, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

A new C 20 -diterpenoid alkaloid from the lateral roots of Aconitum carmichaeli - Jing Yu; Tian-Peng Yin; Jia-Peng Wang; Rui-Feng Mei; Le Cai; Zhong-Tao Ding (Natural Product Research, 2017)

Nurr1 promotes intestinal regeneration after ischemia/reperfusion injury by inhibiting the expression of p21 (Waf1/Cip1) - Guo Zu; Jihong Yao; Anlong Ji; Shili Ning; Fuwen Luo; Zhenlu Li; Dongcheng Feng; Yiqi Rui; Yang Li; Guangzhi Wang; Xiaofeng Tian (Journal of Molecular Medicine, 2017)

Early postnatal stress suppresses the developmental trajectory of hippocampal pyramidal neurons: the role of CRHR1 - Rui Liu; Xiao-Dun Yang; Xue-Mei Liao; Xiao-Meng Xie; Yun-Ai Su; Ji-Tao Li; Xiao-Dong Wang; Tian-Mei Si (Brain Structure and Function, 2016)

Functional analysis of a chitinase gene during the larval-nymph transition in Panonychus citri by RNA interference - Wen-Kai Xia; Xiao-Min Shen; Tian-Bo Ding; Jin-Zhi Niu; Rui Zhong; Chong-Yu Liao; Ying-Cai Feng; Wei Dou; Jin-Jun Wang (Experimental and Applied Acarology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

Curdlan blocks the immune suppression by myeloid-derived suppressor cells and reduces tumor burden - Ke Rui; Jie Tian; Xinyi Tang; Jie Ma; Ping Xu; Xinyu Tian; Yungang Wang; Huaxi Xu; Liwei Lu; Shengjun Wang (Immunologic Research, 2016)

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Archaeal communities in the sediments of different mangrove stands at Dongzhaigang, China - Wei Li; Wei Guan; Huai Chen; Baowen Liao; Ji Hu; Changhui Peng; Junpeng Rui; Jianqing Tian; Dan Zhu; Yixin He (Journal of Soils and Sediments, 2016)

Down-Regulation of ClC-3 Expression Reduces Epidermal Stem Cell Migration by Inhibiting Volume-Activated Chloride Currents - Rui Guo; Fuqiang Pan; Yanping Tian; Hongli Li; Shirong Li; Chuan Cao (The Journal of Membrane Biology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

Upregulation of long noncoding RNA TMEVPG1 enhances T helper type 1 cell response in patients with Sjögren syndrome - Juan Wang; Huiyong Peng; Jie Tian; Jie Ma; Xinyi Tang; Ke Rui; Xinyu Tian; Yungang Wang; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Diagnosis of Small Bowel Obstruction using Targeted Enterography During Nasointestinal Decompression - Rui-hong Li; De-chun Li; Qin-zhong Tian; Ping Wu; Xin-hui Zhang (Cell Biochemistry and Biophysics, 2015)

Surface display of the thermophilic lipase Tm1350 on the spore of Bacillus subtilis by the CotB anchor protein - Huayou Chen; Rui Tian; Zhong Ni; Qing Zhang; Tianxi Zhang; Zhi Chen; Keping Chen; Shengli Yang (Extremophiles, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Ribosomal Protein L3 Mutations are Associated with cfr-Mediated Linezolid Resistance in Clinical Isolates of Staphylococcus cohnii - Hongtao Xu; Rui Tian; Yanming Li; Dongke Chen; Yalin Liu; Yunjian Hu; Fei Xiao (Current Microbiology, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

A Controlled Study of Alprostadil Liposomal Preparation in the Treatment of Blue Toe Syndrome - Hai-lin Xi; Rui Li; Zhi-long Tian; Su Feng; Gao-Lei Jia (Cell Biochemistry and Biophysics, 2015)

The effects of ENSO under negative AO phase on spring dust activity over northern China: an observational investigation - Yun Gon Lee; Jhoon Kim; Chang‐Hoi Ho; Soon‐Il An; Hi‐Ku Cho; Rui Mao; Baijun Tian; Dong Wu; Jae N. Lee; Olga Kalashnikova; Yunsoo Choi; Sang‐Wook Yeh (International Journal of Climatology, 2015)
The effects of El Niño/Southern Oscillation ( ENSO ) under negative Arctic Oscillation ( AO ) phase on the Asian dust activity are investigated for springs of the period 1961–2002. The spring dust index ( DI ) describing the monthly frequencies of three types of dust events (e.g. dust storm, blowing dust, and floating dust) exhibits a significant increase in the years of negative AO phase (hereafter AO −) and El Niño, compared with that in the years of AO − and La Niña. Averaged over all observation stations, the spring DI (49.7) during the El Niño/ AO − years is higher by 11.4% or 29.8% than that (38.3) during the La Niña/ AO − years. We suggest possible physical mechanism that the anomalous large‐scale environments associated with AO − and El Niño are more effective to provide favourable conditions to enhance Asian dust activity. During the El Niño/ AO − years, meridional gradients of pressure and temperature over the dust source regions are significantly enhanced by decreasing the geopotential height and warming air temperature that originated from the north and south of source regions, respectively, under the influence of AO − and El Niño. These also intensify the zonal wind shear and atmospheric baroclinicity, thereby producing enhanced cyclogenesis and dust occurrences over the major source regions. At the same time, dust transport paths with the stronger westerly winds are developed by the combined constraints of anomalous cyclone over the Siberia and the Mongolia and anomalous anticyclone over the western North Pacific, and thus strengthen dust transport to the downwind regions.

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.

A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

An overview of passive and active dust detection methods using satellite measurements - Bin Chen; Peng Zhang; Beidou Zhang; Rui Jia; Zhijuan Zhang; Tianhe Wang; Tian Zhou (Journal of Meteorological Research, 2014)

Semicarbazide – from state-of-the-art analytical methods and exposure to toxicity: a review - Wen-Rui Tian; Ya-Xin Sang; Xiang-Hong Wang (Food Additives & Contaminants: Part A, 2014)

A middle Cambrian shallow water trilobite fauna from the Comstock Formation, near Queenstown, western Tasmania - J. b. Jago; C. j. Bentley; Lin Tian-rui; K. d. Corbett (Australian Journal of Earth Sciences, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Modeling Carbon Fluxes Using Multi-Temporal MODIS Imagery and CO2 Eddy Flux Tower Data in Zoige Alpine Wetland, South-West China - Xiaoming Kang; Yanfen Wang; Huai Chen; Jianqing Tian; Xiaoyong Cui; Yichao Rui; Lei Zhong; Paul Kardol; Yanbin Hao; Xiangming Xiao (Wetlands, 2014)

Structural and energetic insights into the selective interactions of monoacylglycerol lipase with its natural substrate and small-molecule inhibitors - Huayou Chen; Tengyun Sun; Hongzhang Chen; Rui Tian; Tianxi Zhang; Zhi Chen; Zhong Ni (Medicinal Chemistry Research, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Soluble N-terminal fragment of mutant Huntingtin protein impairs mitochondrial axonal transport in cultured hippocampal neurons - Jun Tian; Ya-Ping Yan; Rui Zhou; Hui-Fang Lou; Ye Rong; Bao-Rong Zhang (Neuroscience Bulletin, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

The role of nonlinearities associated with air-sea coupling processes in El Nino’s peak-phase locking - WanSuo Duan; Rui Zhang; YanShan Yu; Ben Tian (Science China Earth Sciences, 2013)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Petrogenesis and tectonics of late Permian felsic volcanic rocks, eastern Qiangtang block, north-central Tibet: Sr and Nd isotopic evidence - Hong-Rui Zhang; Tian-Nan Yang; Zeng-Qian Hou; Yu-Cai Song; Yan Ding; Xian-Feng Cheng (International Geology Review, 2013)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

An approach for the critical coagulation concentration estimation of polydisperse colloidal suspensions of soil and humus - Mingyun Jia; Hang Li; Hualing Zhu; Rui Tian; Xiaodan Gao (Journal of Soils and Sediments, 2013)

Effect of Long-Term Vinasse Application on Physico-chemical Properties of Sugarcane Field Soils - Ze-Pu Jiang; Yang-Rui Li; Guang-Po Wei; Qing Liao; Tian-Ming Su; Yan-Cheng Meng; Hai-Ying Zhang; Chang-Yan Lu (Sugar Tech, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Macronutrients Absorption and Surface Runoff Losses Under Different Fertilizer Treatments in Sugarcane Field - Tian-Ming Su; Yang-Rui Li; Guang-Po Wei; Ze-Pu Jiang; Qing Liao; Shu-Biao Zhu (Sugar Tech, 2012)

Combined effect of sCD40L and PI3K siRNA on transplanted tumours growth and microenvironment in nude mice with gastric cancer - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2012)

CD40 signal expression in gastric cancer tissue and its correlation with prognosis of gastric cancer patients - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2012)

Isolation and characterization of fifteen novel microsatellite loci in golden mandarin fish (Siniperca scherzeri) Steindachne - Min Yang; Xu-Fang Liang; ChangXu Tian; Yasmeen Gul; YaQi Dou; Liang Cao; Rui Yu (Conservation Genetics Resources, 2012)

A new model for cation exchange equilibrium considering the electrostatic field of charged particles - Xin Min Liu; Hang Li; Rui Li; Rui Tian; Jie Hou (Journal of Soils and Sediments, 2012)

Regulation of mesenchymal stem cell differentiation and insulin secretion by differential expression of Pdx-1 - Huijuan Yuan; Hongmei Liu; Rui Tian; Jie Li; Zhigang Zhao (Molecular Biology Reports, 2012)

Gastric cancer cell lines AGS before and after CD40 signal activating - Rui Li; Xue-Qin Pang; Wei-Chang Chen; Ling Li; Wen-Yan Tian; Xue-Guang Zhang (Molecular Biology Reports, 2012)

Involvement of calcium-sensing receptor in oxLDL-induced MMP-2 production in vascular smooth muscle cells via PI3K/Akt pathway - Hong-Xia Li; Fan-Juan Kong; Shu-Zhi Bai; Wen He; Wen-Jing Xing; Yu-Hui Xi; Guang-Wei Li; Jin Guo; Hong-Zhu Li; Ling-Yun Wu; Rui Wang; Guang-Dong Yang; et al. (Molecular and Cellular Biochemistry, 2012)

Gel microbead cultivation with a subenrichment procedure can yield better bacterial cultivability from a seawater sample than standard plating method - Shiqi Ji; Rui Zhao; Qi Yin; Yuan Zhao; Chenguang Liu; Tian Xiao; Xiaohua Zhang (Journal of Ocean University of China, 2012)

Influence of sCD40L on gastric cancer cell lines - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Xue-Guang Zhang (Molecular Biology Reports, 2011)

Molecular and serological diversity in Apple chlorotic leaf spot virus from sand pear (Pyrus pyrifolia) in China - Yansu Song; Ni Hong; Liping Wang; Hongju Hu; Rui Tian; Wenxing Xu; Fang Ding; Guoping Wang (European Journal of Plant Pathology, 2011)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Human Prion Protein Mutants with Deleted and Inserted Octarepeats Undergo Different Pathways to Trigger Cell Apoptosis - Kun Xu; Xin Wang; Qi Shi; Cao Chen; Chan Tian; Xiao-Li Li; Rui-Min Zhou; Yong-Lie Chu; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2011)

Evaluation of Genetic Manipulation Strategies on d-Lactate Production by Escherichia coli - Li Zhou; Zhi-Rui Zuo; Xian-Zhong Chen; Dan-Dan Niu; Kang-Ming Tian; Bernard A. Prior; Wei Shen; Gui-Yang Shi; Suren Singh; Zheng-Xiang Wang (Current Microbiology, 2011)

Foliar and soil 15N natural abundances provide field evidence on nitrogen dynamics in temperate and boreal forest ecosystems - Shu-Lan Cheng; Hua-Jun Fang; Gui-Rui Yu; Tian-Hong Zhu; Jiao-Jiao Zheng (Plant and Soil, 2010)

Extraction of essential oils from garlic (Allium sativum) using ligarine as solvent and its immunity activity in gastric cancer rat - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Analysis of the essential oil of magnolia and its effect on antioxidant enzyme activity, sCD40L and phosphorylate-activate Akt protein levels in gastric cancer mice - Rui Li; Wei-chang Chen; Wei-peng Wang; Wen-yan Tian; Xue-guang Zhang (Medicinal Chemistry Research, 2010)

Synthesis and biological evaluation of cyclopenten-1-one Mannich base oxovanadium compound - Juan Tian; Dongliu Li; Fengying Zhai; Xiaohong Wang; Rui Li (Medicinal Chemistry Research, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Activation of TRPA1 channels by fenamate nonsteroidal anti-inflammatory drugs - Hongzhen Hu; Jinbin Tian; Yingmin Zhu; Chunbo Wang; Rui Xiao; Jeffrey M. Herz; Jackie D. Wood; Michael X. Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Three types of proteinases in Japanese common squid Todarodes pacificus hepatopancreas as studied by using carp myofibrils as substrate - Yuanyong Tian; Emi Umezawa; Rui Duan; Kunihiko Konno (Fisheries Science, 2010)

Microbial community structure and diversity in a native forest wood-decomposed hollow-stump ecosystem - Bao-Yu Tian; Qin-Geng Huang; Yan Xu; Chun-Xiang Wang; Rui-Rui Lv; Jian-Zhong Huang (World Journal of Microbiology and Biotechnology, 2010)

Analysis of synonymous codon usage in Zea mays - Hanmei Liu; Rui He; Huaiyu Zhang; Yubi Huang; Mengliang Tian; Junjie Zhang (Molecular Biology Reports, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Chemical constituents from the fruits of Hippophae rhamnoides - Rui-Xia Zheng; Xu-Dong Xu; Ze Tian; Jun-Shan Yang (Natural Product Research, 2009)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Activities and Toxicity of a Novel Plant Growth Regulator 2-Furan-2-yl-[1,3] Dioxolane - Tian Rui Ren; Yan Hong Xie; Wei Wen Zhu; Yong Hong Li; Ye Zhang (Journal of Plant Growth Regulation, 2007)

Regulation of skeletal muscle differentiation in fibroblasts by exogenous MyoD gene in vitro and in vivo - Rui-feng Qin; Tian-qiu Mao; Xiao-ming Gu; Kai-jing Hu; Yan-pu Liu; Jin-wu Chen; Xin Nie (Molecular and Cellular Biochemistry, 2007)

Functional response of the predator Scolothrips takahashii to hawthorn spider mite, Tetranychus viennensis: effect of age and temperature - Li Ding-Xu; Tian Juan; Shen Zuo-Rui (BioControl, 2007)

FoxO4 is the main forkhead transcriptional factor localized in the gastrointestinal tracts of pigs - Zhen-qi Zhou; Tian Wang; Ling-mei Pan; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2007)

The impact of cropland conversion on environmental effect in the Loess Plateau: a pilot study based on the national experimental bases - Wang Fei; Li Rui; Jiao Feng; Yang Qingke; Tian Junliang (Journal of Geographical Sciences, 2005)

Interaction of DNA-binding proteins with the 5′-flanking region of a cytokinin-responsive cucumber hydroxypyruvate reductase gene - Ge Jin; Maria C. Davey; John R. Ertl; Rui Chen; Zhu-tian Yu; Steven G. Daniel; Wayne M. Becker; Chong-maw Chen (Plant Molecular Biology, 1998)